Experimental investigation of ignition delay and laminar burning velocity of HVO/RP-3 blends as a drop-in aviation fuel under extended operating conditions - Linlin Gu; Xunkai Hu; Chongyang Liu; Dongdong Qi; JingYu Ran; Zhongqing Yang (Fuel, 2027)

Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

hCG orchestrates ovulation in swamp eel (Monopterus albus) via progesterone, metabolic reprogramming, and pyroptosis - Mingsen Zhou; Linlin Wang; Shuo Zheng; Anfu Shen; Xuewen Rao; Liang Ke; Wenhao Hu; Changqing Han; Xiangjiang Liu; Guangfu Hu (Aquaculture, 2027)

Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

The impact of energy structure on sectoral carbon emissions: Evidence from China - Lei Bei; Chaolong Duan; Yongkui Du; Chao Wu; Wentao Li; Hanping Mao; Wu Yang; Ben Wang; Linlin Xu; Ruisi Wang; Xiao Liu; Lushi Sun; et al. (Energy and Climate Change, 2026)

ARHI as a key regulator of EMT and metastasis in pancreatic cancer via the Notch-1 pathway - Jingjing Liu; Yiqun Zhao; Ying Wang; Ying Shi; Qiang Zhi; Linlin Chen; Yuhao Ke; Jianlin Ren (Human Genetics, 2026)

Deposition distribution and optimization of a vertical three-zone counter-spraying device for greenhouse tomatoes - Zhongqing Sun; Yonghua Zhang; Liangchun Qi; Yumei Tang; Pei Wang; Zhenglin Liu; Linlin Yang; Xiuying Tang (Crop Protection, 2026)

KaMYB71 positively regulates drought tolerance in Krascheninnikovia arborescens - Dazhuang Qi; Yuyi Hou; Huihui Liu; Xiaodong Yu; Linlin Zheng; Yingchun Wang (Plant Science, 2026)

Eastward radiation of C4 crops from the Hongshan culture core region initiated around 6 ka - Licheng Guo; Qiaowen Zhang; Shiling Yang; Shangfa Xiong; Zihua Tang; Zhe Liu; Jingyi Cui; Linlin Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The spatial divergence mechanism in the ecological resilience of Qinghai spruce to compound dry-hot extremes across the northeastern Qinghai-Tibet Plateau - Xuan Li; Xiaohua Gou; Dingcai Yin; Linlin Gao; Wenhuo Liu; Dingyun Zhang; Zibo Wang; Jianye Yu (Forest Ecology and Management, 2026)

Synthesis and characterization of porous carbon from Hawaii nut shells for effective CO2 capture - Xiaohan Liu; Yingyi Wang; Zhentao Chen; Xin Hu; Qiang Xiao; Leihong Zhao; Muslum Demir; Murat Kilic; Mohammed K. Al Mesfer; Linlin Wang (Biomass and Bioenergy, 2026)

UPCRISPR: an ultrafast, one-tube multiplexed nucleic acid detection system for resolving the diagnostic gray zone in HPV16/18 detection - Linlin Bai; Dianwei Liu; Chunyan Qian; Weiqi Yuan; Kaiming Guo; Yao Wang; Feng Qian; Mingmin Shi; Bei Wang; Rui Wang (Analytica Chimica Acta, 2026)

MOF-derived carbon membranes for catalytic ozonation: Site-dependent evolution of surface atomic oxygen enables efficient water purification - Guanjin Liu; Linlin Zang; Dongwei Lu; Yinkun Sun; Hui Zhang; Yichao Hu; Zhiyu Sun; Wei Wang; Zhiqiang Sun; Jun Ma (Water Research, 2026)

Physics-informed machine learning of hyporheic exchange driven by channel blockage and riverbed morphodynamics - Hang Li; Linlin Li; Defu Liu; Genguang Zhang; Jiahao Zou; Yu Lei; Canyong Li (Journal of Hydrology, 2026)

Development of low-ammonia MICP technology based on Mg2 +-enhanced nitrogen assimilation and biomineralization - Linlin Zhang; Yue Zhao; Hongyu Han; Ruoxi Li; Zhaofeng Liu; Yuqing Li; Shenghui Yang; Wen Nie (Journal of Environmental Chemical Engineering, 2026)

Ultramicroporous N-doped carbons prepared by KHC2O4 activation for CO2 adsorption - Yujia Yin; Yingyi Wang; Ziyun Li; Ya Liu; Leihong Zhao; Muslum Demir; Aseel Zaid; Linlin Wang; Xin Hu (Journal of Environmental Chemical Engineering, 2026)

Effects of sorghum variety on fermentation microecology and flavor characteristics of sesame-flavor Baijiu - Guihu Zhang; Jiaxin Tang; Chunyan Liu; Linlin Liu; Deyi Zhao; Yansong Xue; Bei-Zhong Han (Food Research International, 2026)

Isolation and characterization of broad-host-range bacteriophages and their alleviation of liver and kidney injury in a mouse model of S. aureus infection - Xinyan Yao; Linlin Huang; Chaoxiang Jia; Dai Peng; Rui Cao; Xiangshun Sun; Yingqian Han; Yang Liu; Yanbin Yang; Guoyu Yang; Yueying Wang; Heping Li (Food Research International, 2026)

Plasma-based biomimetic antigen outpost synergizes with immune checkpoint blockade to enhance antitumor immunity via dual inhibition of SOCS1 and PD-L1 pathways in dendritic cells - Siyuan Meng; Fangnan Lv; Jieqing Chen; Linlin Tao; Hao Guo; Danhui Wang; Jie Sun; Jian Li; Ning Liu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

Optimal grasping direction of a flexible gripper and its RGB-D multimodal estimation method - Jingwei Sun; Linlin Sun; Shuangxi Liu; Huawei Yang; Zixu Chen; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Cerium oxide nanoparticles in agroecosystems: stage-dependent impacts on sorghum growth, forage quality, bioenergy composition, and environmental risk - Linlin Mu; Mahsa Ghorbani; Fatemeh Ganjalikhan Hakemi; Zohreh Ranjbar; Caroline Korte; Bradley Rauh; Gongde Chen; Haizhou Liu; William Bridges; Stephen Kresovich; Christophe J.G. Darnault (Total Environment Advances, 2026)

Representation of western boundary currents under different climatologies with varying horizontal resolutions - Hong Li; Guihua Wang; Fanghua Xu; Lijing Cheng; Junde Li; LinLin Zhang; Yuntao Wang; Wei Li; Haiqing Yu; Zenghong Liu; Zhijin Li (Progress in Oceanography, 2026)

A YjiC-like UDP-glycosyltransferase CtYjiC regulates melanization, infection-related development and virulence in Colletotrichum truncatum - Yulin Qian; Xiaoying Zhai; Qinyi Wang; Jun Liu; Linlin Zhang; Yaxin Zhang; Chunzhi Jin; Long Jin; Kee-Sun Shin; Qin Xiong (Physiological and Molecular Plant Pathology, 2026)

Comparative precipitation forecasting in the Northeastern Tibetan Plateau: Tree-ring reconstruction and future projections using machine learning and CMIP6 models - Longyun Ma; Haoyuan Xu; Jinjian Li; Zeyu Zheng; Linlin Cui; Caihong Liu; Shanlei Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

A hierarchical Bayesian approach to estimate the most probable number (MPN) concentration of Salmonella in raw chicken from qualitative data - Tianmei Sun; Yangtai Liu; Yixuan Li; Linlin Xiao; Xiaojie Qin; Qingli Dong (International Journal of Food Microbiology, 2026)

Bithiophene-engineered carbon nitride with boosted built-in electric field and n-π* transition for PMS activation and 2,4-dichlorophenol degradation - Jihan Zhao; Zhihan Xue; Wei Jiang; Tianyu Zhou; Linlin Liu; Chunbo Liu (Environmental Research, 2026)

Imbalance between regulatory instruments and objectives in China's green building development policies - Linlin Liu (Environmental Development, 2026)

Engineered extracellular vesicle-based microneedle patch via nose-to-brain delivery for enhanced treatment of Alzheimer's disease - Chengxue Pan; Sha Liu; Yue Zhang; Yunxia Li; Linlin Cao; Junli Zhang (Chemical Engineering Journal, 2026)

Porous solar evaporator with hierarchical photothermal structure for highly-performance desalination and water remediation - Yuqian He; Chunguang Liu; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Xi Quan Cheng (Chemical Engineering Journal, 2026)

CH4 displacement and migration during the enrichment of low-concentration coalbed methane by CO2 displacement-assisted vacuum pressure swing adsorption (VPSA) process - Hua Shang; Xiaomin Li; Yang Zhou; Linlin Liu; Jinping Li; Jiangfeng Yang (Chemical Engineering Journal, 2026)

IGF1-IGF1R signaling in tumor-associated macrophages regulates extracellular matrix organization in BRAF inhibitor-targeted melanoma - Ya Luo; Linlin Liu; Xing Zhou; Jiao Yang; Min Tang; Wei Feng; Chunlan Du; Xiaobo Liu; Liu Yang; Fei Liu; Liqun Zhang (Molecular and Cellular Biochemistry, 2026)

Cellulose sulfate-modified biochar loaded with Rs-2 for improving saline-alkali soil - Linlin Zhu; Yao Chen; Nana Liu; Yanhui He; Xiaochen Liu; Qiuyu Chen; Fei Tian; Zhansheng Wu (Soil and Tillage Research, 2026)

Biodegradable piezoelectric suture for real-time biomechanical sensing and therapeutic intervention - Quanhong Hu; Chuyu Tang; Zhirong Liu; Shaobo Wang; Zhuo Wang; Genglin Chen; Shuncheng Yao; Zhuoheng Jiang; Songjing Zhong; Yuxuan Zhang; Linlin Li (Science Bulletin, 2026)

Unveiling urban process-dependent hydrological responses via rainfall “fingerprints” - Ting Liu; Lina Yuan; Yuying Li; Zijiang Song; Linlin Ye; Ao Xu; Tsering Namgyal; Chao Li; Min Liu (Journal of Hydrology, 2026)

Wave-driven core-shell structured cathode SMESs for remediation of phenanthrene and pyrene-contaminated offshore sediments - Haobo Yu; Boyue Liu; Hongying Yuan; Yankai Huang; Yinghao Huang; Tengfei Yuan; Linlin Li; Qi Deng; Jie Li (Journal of Hazardous Materials, 2026)

Synergistic enhancement of heavy rare earth elements leaching from ion-adsorption rare earth ores using fungal metabolites supplemented with ammonium sulfate - Yun Fang; Hailan Wang; Linlin Yan; Jianxiong Zeng; Siqi Chen; Jun Liu; Guowei Wang; Yang Liu; Jun Wang; Chunqiao Xiao (Hydrometallurgy, 2026)

Effect of coupled temperature-humidity drying on multi-scale structure and in vitro digestibility of corn resistant starch - Qing Su; Lirong Chen; Linlin Sun; Xingya Wang; Yuqiu Guo; Meimei Zhao; Kaichang Liu; Kuijie Gong (Food Chemistry, 2026)

High internal phase emulsions stabilised by amyloid fibrils from 7S/11S soybean protein at varying ratios: Study on interfacial behaviour, rheological properties and curcumin delivery potential - Tianlu Han; Ruqi Guo; Yuexin An; Yuyang Huang; Linlin Liu; Zihan Wang; Ying Zhu; Xiuqing Zhu (Food Chemistry, 2026)

Gel-based fascia analogs from soy lipophilic protein and 11S globulin for connective tissue simulation in plant-based meat - Jiyuan Liu; Yixin Zhang; Linlin Liu; Ying Zhu; Yang Li; Mingshou Lv; Bingyu Sun; Xiuqing Zhu; Lianzhou Jiang; Yuyang Huang (Food Bioscience, 2026)

Enzymatic synthesis of oligodextran with prebiotic potential by a recombinant dextransucrase from Latilactobacillus sakei L3 - Binbin Wang; Linlin Hao; Kaiyue Zuo; Xiaojing Liu; Huimin Yao; Weizhong Liu; Fangkun Zhao; Lei Pan; Baomei Wu (Carbohydrate Polymers, 2026)

Role of M1 macrophage-derived exosomes in infantile hemangioma regression via AMPK/SIRT1/PGC1α pathway - LinLin Yue; XiuWen Zheng; XiaoQiang Wen; Yong Zeng; Wei Peng; QianDuo Li; LinShan Zeng; JinPing Liu; Yu Wang; WenQing Fu; HaiJin Liu; Feng Chen (Molecular & Cellular Toxicology, 2026)

Performance and wastewater treatment efficiency of artificially prepared aerobic granular sludge - Xuanzhe Yan; Jinlong Wang; Kailong Liu; Hao Wu; Wei He; Yongmei Zhang; Linlin Tong; Su Li; Zhaoyang You (Biodegradation, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

Tea Rinsing Effectively Mitigates Probabilistic Health Risks From Heavy Metal Exposure - Shuangfei Hu; Linlin Jin; Lili Huang; Cuihong Liu; Minsi Liang; Hongtao Liu (Biological Trace Element Research, 2026)

Microbiological safety of dehydrated foods: risk analysis, technology evaluation, and synergistic strategies for next-generation processing - Yu Wang; Wenchao Liu; Linlin Li; Weiwei Cao; Junliang Chen; Chung Lim Law; Guangyue Ren; Xu Duan (Critical Reviews in Food Science and Nutrition, 2026)

Progressive Failure Behavior of Fracture-Grouted Sandstone After High-Temperature Treatment During Uniaxial Loading: Insights from AE-DIC Experiments and Grain-Based Cohesive Modeling - Haoyang Zhang; Annan Jiang; Fu Zheng; Linlin Liu; Minghao Hao (Rock Mechanics and Rock Engineering, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Phosphate-buffered saline as pH regulators for citrus postharvest handling water, maintain fruit quality by enhancing the phenylpropanoid metabolic pathway - Yanfei Zhu; Huan Liu; Yunxi Xiao; Zhiqiang Xiong; Ling Shen; Jiajun Tang; Zhifeng Zhu; Linlin Zhong; Rangwei Xu; Quan Sun; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

Modified grafted starch flocculant for the treatment of coal chemical gasification gray water: Synergistic turbidity and hardness removal - Lixin Li; Sinan Liu; Fan Yang; Mingyu Han; Zilong Dong; Caiyu Sun; Linlin Huang; Zhichao Feng; Miyi Luo; Lizhi Tian (Journal of Water Process Engineering, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Spatial heterogeneity of wildfires in Southern China during the Last Glacial Maximum - Binxu Liu; Jia Liu; Xingyuan Qin; Linlin Chen; Jiaxi Zhou; Zhiyun Lu; Robert A. Spicer; Shufeng Li; Tao Su (Global and Planetary Change, 2026)

Lactobacillus paracasei PC18 fermentation enhances the functional and hypoglycemic properties of soluble dietary fiber from lotus root residue. - Hongzhi Zhang; Lingyu Li; Anthony Pius Bassey; Zhiwei Fu; Yongsheng Zhu; Kaiyan Liu; Linlin Fan; Xiaoli Liu (Food Research International, 2026)

Effects of the foliar application of selenite at different growth stages on selenium transformation, silage quality and the metabolome of tiger nut (Cyperus esculentus L.) - Kexin Wang; Ting Gong; Xinge Du; Wei Liu; Ruize Sun; Chenghao Che; Yilin Zou; Shengnan Sun; Linlin Mei; Guofu Hu (Food Chemistry, 2026)

Lymph node–targeting GM-CSF vesicles produced in situ by ultrasound-activated bacterial factories for enhanced immunotherapy - Yue Yuan; Beibei Zhang; Shaobo Duan; Ruiqing Liu; Juan Zhang; Rui Zhang; Qi Zhou; Linlin Zhang; Xiaoxia Xu; Zesheng Li; Yuanyuan Liu; Xiaoxiao Li; et al. (Chemical Engineering Journal, 2026)

Pharmacovigilance insights into drug-induced hypercalcemia: evidence from the U.S. FDA Adverse Event Reporting System (FAERS) database - Wensheng Liu; Linlin Wang; Xue Song; Xuan Ye; Yunlan Ding; Jiyong Liu; Qiong Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

NCAPG reprograms glycolytic and lipid metabolism by sustaining glycerophospholipid flux in small-cell lung cancer - Yang Sun; Jinglin Wen; Rui Su; Linlin Liu (Molecular and Cellular Biochemistry, 2026)

Characterizing functional connectivity gradients for the hippocampus–amygdala complex in healthy and psychiatric cohorts - Xiang-Shen Liu; Janna N. Vrijsen; Linlin Yan; Koen V. Haak; Rose M. Collard; Philip F. P. van Eijndhoven; Christian F. Beckmann; Guillén Fernández; Indira Tendolkar; Nils Kohn (Brain Structure and Function, 2026)
The hippocampus and amygdala play essential roles in human cognition and emotion, through their extensive connectivity with other brain regions and close interaction between them. Uncovering the functional organization of the hippocampus–amygdala complex and its relationship with neurotransmitter distribution can enhance our understanding of their biological functionality, and provide a basis for further exploration of the clinical relevance. An emerging functional connectivity analysis method termed connectopic mapping, may offer a novel approach to characterize this functional organization. In this study, we applied connectopic mapping to the hippocampus-amygdala complex, testing its utility with resting-state functional magnetic resonance imaging (fMRI) scans of two independent datasets: one comprising healthy individuals ( N = 410) and another comprising a psychiatric cohort ( N = 367). The spatial organization of derived gradient maps was compared to 18 positron emission tomography (PET) or single photon emission computed tomography (SPECT) scan templates for different neurotransmitter systems. Individual gradient–neurotransmitter similarity indices were correlated with mental health outcomes. Our analyses identified six distinct gradient maps in both datasets. The third-order gradients showed stable similarity with 5-HT1A receptor maps across various resting-state scans. Similarities were also observed between gradient maps and the distribution patterns of neurotransmitters within the dopaminergic system. Individual gradient-to-5-HT1A similarity was positively correlated with depressive severity and anxiety sensitivity, highlighting the psychopathological relevance. These findings demonstrate that across the psychiatric continuum, connectopic mapping is a powerful tool for exploring the relationship between functional connectivity organization and neurotransmitter distribution, showing potential as a comprehensive transdiagnostic biomarker.

Impact of environmental factors on the distribution characteristics of phytoplankton functional groups in Beijing - Linlin Qin; Xu Han; Ting Zhu; Yixuan Zhang; Na Cui; Yuepeng Liu; Wenyan Liang (Protist, 2026)

Effects and mechanisms of a novel multi-target regulator on serum uric acid reduction and renal injury improvement in rats with hyperuricemia and renal damage - Zhihua Xing; Yue Xu; Wen Jiang; Zhiyuan Xu; Guanghuan Shen; Na Ling; Mingyu Gao; Weina Han; Yingjie Liu; Linlin Cui (PharmaNutrition, 2026)

Built-in electric field engineering in boron and bithiophene Co-doped carbon nitride for boosting photodegradation: Mechanism and toxicity assessment - Siyi Wang; Ting Wang; Liang Wang; Tianyu Zhou; Linlin Liu; Chunbo Liu (Journal of Environmental Chemical Engineering, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

Breaking the trade-off: A phosphorylated interpenetrating network bridging ion-conduction pathways for safe and high-performance solid-state batteries - Yuyang Wang; Linlin Wang; Jie Yang; Qiuya Wang; Junye Zhang; Cheng Liu; Zaichao Zhang; Le Xu; Rundong Chen; Tianchen Shen; Shigang Lu; Luyang Chen (Chemical Engineering Journal, 2026)

Responses of sedimentary magnetic susceptibility and metal contents to climate and anthropogenic activity changes: examination on lake records across the Asian monsoon region - Haiyang Yu; Shuangchi Liu; Jule Xiao; Xu Wang; Linlin Cui; Licheng Guo; Xueting Wang; Shihao Zhang (CATENA, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

ABEEM/MM Magnesium Force Field for Proteins and Aqueous Solutions - Jing Zhang; Linan Lu; Runqiang Yu; Linlin Liu; Lei Wang; Cui Liu; Lidong Gong; Zhongzhi Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Linking genetic connectivity and ecological niche similarity to inform coastal biosecurity management: a global case study of Mytilopsis sallei - Hao Dong; Linlin Zhao; Liuyi Huang; Xiaoyang Wang; Changdong Liu (Ocean & Coastal Management, 2026)

PCBs exposure and renal injury: comprehensive assessment strategy based upon TRAEC strategy - Zhiyuan Chen; Changqian Liu; Linlin Zhang; Jianrong Han; Xiaoyan Ding; Changshun Han; Sihao Zhu; Jiabao Cao; Jiaxin Song; Fucong Zhang; Jian Li; Zhenghong Zuo; et al. (Journal of Environmental Management, 2026)

Polyphenol oxidase-mediated browning during storage of Pinus elliottii oleoresin: characterization of pine-needle PPO and antibrowning action of L-cysteine - Siheng Zhang; Hanxiao Liu; Jingcong Liu; Lu Qin; Xin Li; Xuanrou Wei; Xiaopeng Chen; Linlin Wang (Food Bioscience, 2026)

Unlocking iron-chromium flow batteries: Conquering kinetics and crossover for affordable grid storage - Jiaxin Meng; Guozhen Zhang; Weizhai Bao; He Liu; Cong Guo; Jingfa Li; Feng Yu; Linlin Yang; Aishui Yu (Chemical Engineering Journal, 2026)

Effects of combined selenium and sulfur application on glucosinolate biosynthesis in Chinese cabbage sprouts - Huixia Bai; Linlin Zhao; Yafang Luo; Qi Hu; Lingling Liu; Yang Chen; Huan Wang; Yushu Wang (Physiology and Molecular Biology of Plants, 2026)

Advances in bacterial synthesis pathways of bioflocculants and their applications in mine wastewater treatment - Linlin Zhang; Zhaofeng Liu; Qiang Guo; Jiawei Tang; Xiaoduan Li; Qun Wang (World Journal of Microbiology and Biotechnology, 2026)

KansFormer network based on a multimodal cross-attention mechanism for drug-target interaction prediction - Anting Gao; Yuandong Liu; Kai Che; Longbo Zhang; Yifeng Gao; Linlin Xing (Molecular Diversity, 2026)

Penicinoid A, an undescribed sesterterpenoid with cytotoxic activity from Penicillium herquei - Mengyi Deng; Enrui Zhang; Fengtai Qiu; Yingying Fei; Yuyan Liu; Linlin Li; Yiyang Xiong; Xianli Zhou (Natural Product Research, 2026)

Quantitative identification of anthropogenic sources of metal(loid)s in river sediments from a small watershed based on APCS-MLR and MixSIAR model - Yao Wei; Fen Xu; Qiang Liu; Chunmei Jiang; Linlin Bao (Marine Pollution Bulletin, 2026)

Hydrogeochemical properties and health risks of high-fluoride groundwater in southern Jiaolai Basin - Menghan Tan; Zongjun Gao; Jiutan Liu; Bing Jiang; Linlin Lin; Qiang Li; Yiru Niu (Process Safety and Environmental Protection, 2026)

Built-in electric field constructed by asymmetric electron cloud distribution for facilitating photocatalytic H2O2 production in covalent organic frameworks - Chuanxue You; Yue Zhou; Meiting Yang; Jingyang Li; Bo Hu; Yunchao Ma; Linlin Liu; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Unlocking circularity in rural waste management in northwest China: A systematic framework to quantify energy-environment-pollution nexus - Yuansheng Huang; Linlin Wang; Yi Liu; Yihan Chen; Xinglin Zhang; Yiliang He (Journal of Cleaner Production, 2026)

Bioaugmentation of thiourea-acclimated biomass relieves thiourea’s inhibition of nitrification - Meng Huang; Xiaobing Gao; Ning Yan; Fei Liu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Environmental Chemical Engineering, 2026)

Association of prenatal exposure to polychlorinated biphenyls with cleft lip and/or palate risk in offspring: A case-control study - Sainan Li; Shujian Lin; Yongyan Chen; Yiqi Ding; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Environmental Sciences, 2026)

Characterization of a novel lytic Mooglevirus phage to control Salmonella Senftenberg and its application in foods - Jiayi Xue; Tingyu Liu; Linlin Xiao; Jiuchao Zhu; Yi Hong; Xiang Wang; Jinghang Zhang; Hengyi Hu; Zhuosi Li; Qingli Dong; Xiaojie Qin (Food Control, 2026)

Cyclic performance of dual stage energy dissipation joints for connecting CFST column and exterior wide-flat beam - Mingyang Wei; Linlin Song; Jianhua Zhang; Cheav Por Chea; Yan Geng; Xueming Zhang; Dianwei Gao; Zhicheng Liu (Engineering Structures, 2026)

Edge-cloud collaborative digital twin for vibration anomaly detection and localization in high-rise buildings - Chen Xiong; Huijin Zhu; Jie Huang; Kuangyu Chen; Weizong Lai; Linlin Xie; Liu Mei (Engineering Structures, 2026)

Study on the Separation of Co(II) Ions by Triethylenetetramine-Modified Polyacrylonitrile Nanofibers - Yang Luo; Shuyuan Liu; Weiwei Li; Guangchuan He; Guangfu Chen; Xianchen Huang; Xiangyang Niu; Jiahui Ruan; Linlin Huang; Guoyuan Yuan (Water, Air, & Soil Pollution, 2026)

Association Between Maternal Exposure to Eight Metals at Everyday or Low Levels During the Periconceptional Period and Risk for Fetal Congenital Heart Defects: A Case-Control Study in China - Xin Pi; Chunyi Liu; Xiaoqian Jia; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

Soil bacterial community assembly and driving factors in wetlands along the southern margin of the Tarim Basin - Linlin Zhang; Peishan Zhao; Guanglei Gao; Guodong Ding; Ying Zhang; Qiyan Li; Yilin Liu (Applied Soil Ecology, 2026)

Ultrastructural Evidence of Altered Dendritic Morphology in the Prefrontal Cortex of Alzheimer's Model Rats - Jinyue Guo; Jing Liu; Yanchao Zhang; Jiazheng Liu; Hao Zhai; Linlin Li; Hua Han (Neuroscience Bulletin, 2026)

Eco-friendly asphalt: Emission reduction and performance enhancement with a novel fume suppressant - Shangheng Zeng; Ghim Ping Ong; Shi Xu; Hongyue Liu; Linlin Liu; Jianying Yu (Transportation Research Part D: Transport and Environment, 2026)

Non-isothermal kinetic study on the roasting system of waste LiNixCoyMn1-x-yO2 battery powder-sulfamic acid - Zhenning Liu; Zhenan Jin; Linlin Tong; Xiaohang Ren; Guorui Hou (Process Safety and Environmental Protection, 2026)

Microstructural changes, water migration, and oil release in Camellia oleifera seeds during microwave vacuum drying - Jianan Gao; Guangfei Zhu; Guangyue Ren; Jian Li; Yongli Zhang; Jianfang Shi; Wenchao Liu; Linlin Li; Xu Duan (Journal of Stored Products Research, 2026)

Coastal land reclamation induced estuarine nutrient-related eutrophication stressors: phenomena, evaluation and management strategies - Linlin Wang; Yuehua Guo; Wenbin Liu; Huaihao Shao; Shuangliang Dai; Lin Mu; Xianzhong Mao; Hongsheng Bi; Kai Zhou; Xiaoyu Lei (Journal of Hydrology, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Selective separation of rare earth from acetatesolution containing aluminum by nonequilibrium extraction - Linlin Chang; Jian Li; Dongyue Xie; Xudong Liu; Yaobin Lai; Jiayi Zan; Chenjiahui Wang; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Journal of Environmental Management, 2026)

Source and accumulation of helium in the Dongsheng gas Field, Ordos Basin, China: Insights from noble gas isotopes - Yu Gao; Shuangjian Li; Xiaoqi Wu; Dongya Zhu; Pengpeng Li; Linlin Wang; Guangxiang Liu; Jiahao Lv; Jiarun Liu; Quanyou Liu (Journal of Asian Earth Sciences, 2026)

Tailoring monoglyceride oleogel crystallization by eutectic and crystal nucleation disturbance: functional frozen specialty fat for use in croissants - Yanxia An; Yi Han; Ziwei Liu; Jingyuan Su; Jian Zhang; Keke Liu; Linlin Li (Food Research International, 2026)

Advances in the effect of the structure of high-moisture extruded plant-based meat on in vitro digestive properties - Yuyang Huang; Yixin Zhang; Yang Gao; Ying Zhu; Bingyu Sun; Linlin Liu; Jiyuan Liu; Baoning Zheng; Mingshou Lv; Lianzhou Jiang; Xiuqing Zhu (Food Research International, 2026)

Amyloid fibrillation of different ratios of 7S/11S soy protein: comparison of fibril structural characteristics and analysis of the potential for preparing high-internal-phase emulsions - Tianlu Han; Lidan Qiu; Qinlin Hu; Ruqi Guo; Ying Zhu; Yuyang Huang; LinLin Liu; Ying Wang; Xiuqing Zhu (Food Hydrocolloids, 2026)

Occurrence, composition profiles, and human exposure assessment of liquid crystal monomers in indoor dust from Wuxi, China - Yiyang Yao; Linlin Wu; Run Zhou; Xi Wang; Yan Gong; Rong Chen; Wenwei Liu (Environmental Pollution, 2026)

Synergistic effects of crystal-facet on dehalogenation kinetics and poison tolerance of Pd-based electrocatalytic membranes for efficient removal of halogenated pollutants - Yinkun Sun; Dongwei Lu; Xianci Pan; Rongxin Zeng; Zhiyu Sun; Xueying Chen; Yumei Wang; Qingcan Zhou; Yichao Hu; Linlin Zang; Guanjin Liu; Jun Ma (Chemical Engineering Journal, 2026)

Holocene wildfire activity archived in East Asian marginal sea: Linkages to climate variability and human civilization - Linlin Chen; Yazhi Bai; Zhigang Guo; Weini Chong; Yuying Zhang; Jinming Bai; Yaru Liu; Haiyan Fang; Limin Hu (CATENA, 2026)

Seasonal-spatial distribution and prevailing wind analysis of Martian dust devils in Amazonis Planitia using a multi-scale attention network - Linlin Shi; Gan Liu; Jialong Lai; Xu Ma; Feifei Cui; Xiaoping Zhang; Yi Xu; Qiquan Yang (Science China Earth Sciences, 2026)

Mechanism of liver fibrosis induced by life-long triclosan exposure in offspring rats: an adverse outcome pathway framework validated by in vivo and in vitro experiments - Fu Liu; Jianing Shang; Linlin Zheng; Xiaoyu Zhang; Anqi Cui; Xue Dou; Yunwei Li; Jieyu Liu (Archives of Toxicology, 2026)

Exploring the necessity of low-carbon transition of power dispatching: a perspective of environmental efficiency assessment - Jingliang Jin; Linlin Li; Wei Ben; Chenxi Li; Tingting Liu; Jizhe Zheng (Environment, Development and Sustainability, 2026)

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

Decadal climate control of circulation regime transitions in a large marginal sea - Lixia Zheng; Zhongya Cai; Jianping Gan; Chiwing Hui; Linlin Liang; Hiusuet Kung; Zhiqiang Liu (Science Bulletin, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Analysis of shrinkage deformation behavior in microwave vacuum drying of Chinese yam based on evolution of physical properties - Qian Zhou; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Tongxiang Yang; Junliang Chen; Guangyue Ren; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Iron-induced charge density redistribution of medium entropy alloys for ampere-level seawater electrolysis - Luyu Liu; Xiang Ding; Jun Xiang; Haotian Qin; Siyuan Tang; Linlin Xu; Jianling Dong; Yin Yin; Nan Jiang; Xinchun Yang; Fuzhan Song (Fuel, 2026)

Unveiling structural evolution during high-moisture extrusion of soy protein isolate-wheat gluten systems with soy dietary fiber: A sudden shutdown-based study - Ruqi Guo; Haojia Zhang; Yang Gao; Zihan Wang; Yinlin Wang; Ying Zhu; Linlin Liu; Xiuqing Zhu (Food Chemistry, 2026)

Meteorological observation research based on an improved EfficientNetV2 model - Haozheng Yin; Yu Cao; Linlin Liu; Dan Chen; Qiong Zhang (Environmental Modelling & Software, 2026)

Integrated multi-energy hybrid systems for net-zero buildings: Dynamic simulation, lifecycle 4E assessment, and multi-objective optimization - Manfeng Li; Mengke Liu; Guofeng Zhou; Linlin Zhang; Panpan Li; Yiji Lu (Energy and Buildings, 2026)

Enhanced selectivity for the removal of Al3+ from the simulated rare earth leachate via a 3D electrochemical hydrolysis process - Chenjiahui Wang; Jian Li; Dongyue Xie; Xudong Liu; Jiayi Zan; Linlin Chang; Yaobin Lai; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Desalination, 2026)

Black phosphorus with enhanced stability via palladium induced electronic structure modulation and its application in portable breath acetone sensing - Guangliang Li; Yunzhu Liu; Lei Ma; Hang Zhang; Jinlong Ma; Linlin Hou; Jian Duan; Guanglan Liao; Hu Long; Tielin Shi (Chemical Engineering Journal, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Oxygen vacancy induced strong interaction of single atom Ru with In2O3 for improved CO2 hydrogenation to methanol - Shilong Xiong; Song He; Linlin Wu; Haibo Zhao; Chang-jun Liu (Chemical Engineering Journal, 2026)

Consolidated bio-saccharification (CBS) enhanced hydrogen production via bioaugmentation to eliminate cellobiose inhibition: Investigation on hydrogen production performance and microbial community - Sheng Tao; Song Chengwei; Liu Qianchi; Song Zhiwei; Yang Chunxue; Sun Caiyu; Li Lixin; Huang Linlin; Wang Miao (Biocatalysis and Agricultural Biotechnology, 2026)

Bone mesenchymal stem cells attenuate axonopathy in spinal cord of rats exposed to 2,5-hexanedione via NGF-dependent and -independent pathways - Qiufang Bai; Zhe Li; Jing Chen; Man Liu; Xiaodan Shao; Xiaochi Chen; Fengyuan Piao; Linlin Fang (Molecular and Cellular Biochemistry, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

Tracing nitrate sources and transformations using nitrogen and oxygen isotopes in the second largest freshwater lake of China - Zhengjie Li; Guitao Shi; Yilan Li; Linlin Song; Yanhua Zhang; Yi Shi; Wei Zhang; Shuguang Liu; Weizhi Lu (Journal of Hydrology, 2026)

From association to mechanism: Prenatal PFAS Co-exposures induces fetal neural tube defects via autophagy-mediated ferroptosis - Yongyan Chen; Qianhui Cheng; Chen Yang; Sainan Li; Hai Lin; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2026)

Engineered microbial consortium enhances tomato salt tolerance through rhizosphere modulation for sustainable crop production - Linlin Sun; Xinyu Jia; Xiaohu Zhou; Junsong Yue; Zihe Deng; Muhammad Saad Ahmed; Xiaochen Liu; Zhansheng Wu (Journal of Cleaner Production, 2026)

Comparative metabolomic analysis of spray- and freeze-dried Cornus officinalis microcapsules reveals temperature-dependent flavonoid retention and optimal encapsulation conditions - Wenchao Liu; Xinyu Wei; Lijuan Wang; Linlin Li; Weiwei Cao; Yilin Huang; Junliang Chen; Chung Lim Law; Qing Sun; Guangyue Ren; Xu Duan (Innovative Food Science & Emerging Technologies, 2026)

Inactivation of Penicillium ochrochloron spores by pulsed light: Mechanism and preservation efficacy in strawberries - Xiaozhen Cui; Anthony Pius Bassey; Fan Wang; Shudong Xie; Dongnan Li; Linlin Fan; Yongsheng Zhu; Li Bin; Xiaoli Liu (Food Control, 2026)

The effect of yeaZ on formation and resuscitation of viable but nonculturable (VBNC) Salmonella enteritidis serovar enteritidis - Yuyang Jiao; Aiqi Yang; Xin Yu; Jiayu Yu; Jianlong Zhang; Linlin Jiang; Yao Li; Yang Liu; Hongwei Zhu; Xingxiao Zhang (Food Microbiology, 2026)

Humidity-regulating antibacterial trilayer Janus membrane of polyacrylonitrile/gelatin-potato starch/polycaprolactone-cinnamon essential oil for cherry tomato preservation - Mingyi Tian; Chenlong Liu; Zhiyuan Ge; Wei Ji; Yimeng Zhang; Linlin Li; Hualin Wang (Food Packaging and Shelf Life, 2026)

Synergistic DFT and experimental design of Ga/W Co-Doped SnS2 microspheres with enriched sulfur vacancies for enhanced NO2 sensing - Wei Zhao; Lanlan Guo; Xin Shi; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2026)

A machine learning-based model for aerosol scattering hygroscopic growth factor (f(RH)) prediction in Beijing urban area - Hongfei Tong; Xinyao Hu; Can Xia; Xiaojing Shen; Yangmei Zhang; Quan Liu; Lei Liu; Linlin Liang; Jiayuan Lu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2026)

The Key Role of Somatostatin Neurons in the Suprachiasmatic Nucleus in Anxiety-Depression Comorbidity Following Sleep Deprivation - Yifei Zhang; Yuxin Wang; Xinyue Liu; Chunlin Ren; Ming Chen; Linlin Bi (Molecular Neurobiology, 2026)

Deciphering Ferroptosis-Related Astrocyte Subpopulations and Diagnostic Biomarkers in Parkinson’s Disease through RNA Transcriptomics - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Mingshuo Sun; Linlin Wang; Tianman Zhao; Zhiyun Wang; Xue Xue (Molecular Neurobiology, 2026)

Effect of cAMP concentration on apoptosis of sheep granulosa cells in vitro - Wenhao Wang; Linlin Pei; Peilin Guo; Andi Qiao; Shuyan Guo; Xin Xu; Chunjie Liu (In Vitro Cellular & Developmental Biology - Animal, 2026)

Seismic performance of a new type of sliding-rolling friction composite isolation bearing - Bo Liu; Danguang Pan; Congbo Song; Linlin Liu; Guowei Ni (Earthquake Engineering and Engineering Vibration, 2026)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Apple diameter prediction during mechanical picking based on flexible force-sensing and CNN-BiLSTM-Attention method - Mingyang Lu; Linlin Sun; Haidi Chu; Mochen Liu; Jing Wang; Hongjian Zhang; Zhanhua Song; Yao Lu; Jinxing Wang; Yinfa Yan (Computers and Electronics in Agriculture, 2025)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

LARS1 knockdown suppresses the biological activities of thyroid cancer cells by stimulating autophagy - Congwen Jin; Chuanhong Li; Linlin Chen; Hao Liu; Yousheng Yu; Benxin Chen (Tissue and Cell, 2025)

Impacts of climate change and land use changes on heat island effect in the Guangdong-Hong Kong-Macao Greater Bay Area under the SSP-RCP framework - Xin Yan; Alex Hay-Man Ng; Xun Liu; Qianqian Zhou; Linlin Ge (Sustainable Cities and Society, 2025)

Filamentous cyanobacterium Spirulina platensis mediates phosphate biomineralization for efficient fluoride immobilization and drives metabolic shift toward stress resistance and biomineralization - Linlin Cui; Zhilian Liu; Jun Suo; Yun Liu; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Hazardous Materials, 2025)

The gold, palladium, silver, copper, and silicon were synergistically recovered from the waste chips through the phase reconstruction and stepwise recovery methods - Shuo Liu; Yaobin Lai; Xin Chen; Jian Li; Hui Zhang; Linlin Chang; Tianyi Chen; Xuxia Zhang; Yangyang Xie; Liuyimei Yang; Tao Qi (Journal of Environmental Chemical Engineering, 2025)

Study on slow pyrolysis mechanism of non-metallic fractions in waste printed circuit boards using TG-FTIR-MS analysis - Lushi Sun; Gan Wan; Tao Chen; Jiaxing Du; Linlin Xu; Haitao Liu (Journal of Environmental Management, 2025)

Aminated lignin-modified polyethersulfone membranes with enhanced antifouling performance for oil-water separation - Linlin Liang; Meijiao Peng; Hui Xu; Zijun Wu; Baojie Liu; Chengrong Qin; Chen Liang; Caoxing Huang; Shuangquan Yao (Journal of Environmental Chemical Engineering, 2025)

Transition cavity structure and SPI-WG ratios mediated the porous fibrous structural morphology changes of high-moisture extrudates - Yang Gao; Yihan Song; Ying Zhu; Yuyang Huang; Linlin Liu; Lianzhou Jiang; Xiuqing Zhu (Food Research International, 2025)

Inhibitory effects of nisin and ε-polylysine on the microbial cell structure and physiological function of Bacillus amyloliquefaciens and applications in bread preservation - Min Qu; Xin Zhang; Xiuqing Zhu; Jingbo Kang; Linlin Liu; Mingshou Lv; Ying Zhu; Bingyu Sun (Food Bioscience, 2025)

Effect of salt stress-induced germination technology on the phenolic composition, antioxidant capacity, and metabolic pathways of highland barley (Hordeum vulgare L.): A metabolomics insight - Shuyao Wen; Disheng Xiao; Linlin Ye; Shimin Liu; Miao Liu; Xiaoyi Hou; Hui Li; Na Deng; Jianhui Wang (Food Bioscience, 2025)

Ultrasensitive, signal-complementary piezo-capacitive pressure sensor for complex physiological monitoring and HMI - Daojian Su; Linlin Jiang; Zijun Pan; Changhong Yang; Chang Liu; Rongxiao Liu; Tong Liu; Xin He; Shifeng Huang; Zhenxiang Cheng (Chemical Engineering Journal, 2025)

Microwave-assisted modification for enhancing the slow-release performance of biochar-based fertilizer and application - Linlin Zhu; Bingzhe Su; Chen Guan; Yao Chen; Dongye Huang; Jiayao Zhou; Qiuyu Chen; Xiaochen Liu; Fei Tian; Zhansheng Wu (Journal of Soils and Sediments, 2025)

CUR-PDT induces ferroptosis of RA-FLS via the Nrf2/xCT/GPX4 pathway to inhibit proliferation in rheumatoid arthritis - Lihua Sun; Yajuan Niu; Bo Liao; Linlin Liu; Yi Peng; Kaiting Li; Xinhua Chen; Qing Chen; Dingqun Bai (Inflammation Research, 2025)

ViruSeg: Harnessing the Power of Large Language-Image Model for Enhanced Virus Image Segmentation - Shengxiang Wang; Xiangzheng Fu; Zhenya Du; Xinxin Liu; Qiaochu Mai; Linlin Zhuo; Boqia Xie; Quan Zou (Interdisciplinary Sciences: Computational Life Sciences, 2025)

NTMFF-DTA: Prediction of Drug-Target Affinity Based on Network Topology and Multi-feature Fusion - Yuandong Liu; Youzhi Liu; Haoqin Yang; Longbo Zhang; Kai Che; Linlin Xing (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Remediation of alkaline cadmium (Cd) contaminated soil through biochar combined with organic fertilizer application - Linlin Liu; Jie Hu; Di Miao; Wenxin Yin; Wenping Sun; Lianglun Sun; Meizhen Tang (Environmental Geochemistry and Health, 2025)

Multi-parameter input damage limit prediction for bare reinforced concrete frames using XGBoost - Chen Xiong; Yuchao Cao; Jingfeng Zheng; Linlin Xie; Liu Mei; Lixiao Li; Wujian Long (Soil Dynamics and Earthquake Engineering, 2025)

Does soil compaction affect the mobility and transformation behavior of Arsenic -A case study of an Alfisol - Xinjun Huang; Lanting Liu; Yali Wang; Yongqiang Yang; Linlin Zhao; Rainer Horn; Liping Li (Soil and Tillage Research, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Investigating the aroma transition during rapid mango ripening driven by dynamic catabolism of fatty acids - Yuanping Wang; Zhenjiang Zhou; Yonghao Liu; Rongli Pang; Xi Zhao; Qi Chen; Linlin Guo; Baiyi Lu (Food Chemistry, 2025)

Effects of ultrasound on the structure and properties of soy protein gels prepared with different 11S/7S ratios - Lidan Qiu; Ying Zhu; Xiuqing Zhu; Linlin Liu; Mingshou Lv; Yuyang Huang; Bingyu Sun; Min Qu (Food Hydrocolloids, 2025)

Seismic performance of rubberized concrete double-column piers confined by corrugated steel tubes - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Atmospheric and room temperature plasma mutagenesis of Graesiella emersonii for enhanced protein production using methanol as novel carbon source - Jixu Luo; Guanqin Huang; Mingjia Zheng; Changqing Ou; Qingyue Chen; Yufeng Ling; Linlin Cai; Yang Yang; Lingcheng Liu; Fei Huang; Zhangli Hu; Yihong Zheng (Bioresource Technology, 2025)

Hyperbaric oxygen treatment mitigates gut dysbiosis of mice with spinal cord injury - Mo Liu; Lu Yang; Ding Nan; Linlin Ma; Jing Zhang; Fang Liang; Jing Yang; Xuehua Liu (Journal of Molecular Medicine, 2025)

An MA-film platform designed for high-throughput synthesis of calcium phosphates screening amino acid on collagen film - Xiaoyu Li; Xiran Yang; Xinkun Chen; Changxia Liu; Linlin Wu; Dazhuo Qiu; Xueye Chen; Xuetao Shi (Analytica Chimica Acta, 2025)

DBENet: dual-branch encoder network based on the visual state space model for semantic segmentation of remote sensing image - Hengyou Wang; Hao Liu; Lianzhi Huo; Linlin Chen; Qiang He (International Journal of Remote Sensing, 2025)

Facile One-Pot Synthesis of Folic Acid-Derived Carbon Dots for Selective “on-off-on” Fluorescence Detection of Ag+ and Glutathione with High Sensitivity - Lijuan Chen; Yuting Ding; Changchang Chen; Xiaoyan Jiang; Danni Yang; Jingwen Li; Hong Liu; Linlin Yang (Journal of Fluorescence, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

A probabilistic formula for sediment incipient motion on combined sloping beds by considering the hiding-exposure effect - Linlin Li; Hang Li; Genguang Zhang; Yao Xiao; Defu Liu; Yu Lei; Maohua Le (Hydrological Sciences Journal, 2025)

Triboelectric force feedback-based fully actuated adaptive apple-picking gripper for optimized stability and non-destructive harvesting - Jingwei Sun; Linlin Sun; Guangze Zhao; Junsheng Liu; Zixu Chen; Linlong Jing; Xinpeng Cao; Hongjian Zhang; Wei Tang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Predicting seasonal distribution and inter-seasonal migration corridors for three subspecies of common minke whales - Linjie Li; Linlin Zhao; Shiji Xu; Changdong Liu; Yanli Tang (Ocean & Coastal Management, 2025)

Spatial planning for dugong conservation: Assessing habitat suitability and conservation gaps in Indo-Pacific Convergence Zone - Bei Wang; Kaiyu Liu; Watchara Sakornwimon; Wenhao Huang; Tingting Li; Xianshui Lai; Chengcheng Li; Linlin Zhao; Bailin Cong; Shenghao Liu (Marine Policy, 2025)

Ion channels: beyond native mass spectrometry - Ronald J. Quinn; Yushu Gu; Miaomiao Liu; Linlin Ma (Phytochemistry Letters, 2025)

Novel thin film nanocomposite membranes developed via polydopamine nanoparticles, Halloysite nanotubes and Cu-MOF nanosheets for dye removal - Junfeng Zheng; Jinyu Liu; Zikang Qin; Yulei Ma; Yahui Yang; Linlin Yang; Hang He; Zhongde Dai; Wenju Jiang; Lin Yang; Lu Yao; Bo Tang (Journal of Environmental Chemical Engineering, 2025)

Boosting dynamic NH3 adsorption performance of UiO-66 via amino-induced local polarization - Zimu Liu; Mingtai Li; Zitong Zhao; Yulong Yang; Linlin Deng; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Simultaneous fluoride, calcium, and phosphorus removal by bacterial phosphate mineralization: Reaction pathways, mechanisms, and process optimization - Linlin Cui; Zhilian Liu; Jun Suo; Jue Kang; Yun Liu; Guanzhou Qiu; Hongbo Zhao; Li Shen (Journal of Environmental Chemical Engineering, 2025)

Hematopoietic responses to metal-organic frameworks in adult mice following pulmonary exposure - Min Li; Linlin Yao; Yuanyuan Wang; Jie Gao; Junjie Ma; Yaquan Liu; Yun Ding; Xuehan Zheng; Liqun Chen; Runzeng Liu; Li Zeng; Guangbo Qu; et al. (Journal of Environmental Sciences, 2025)

Enhanced selective oxidation of 5-Hydroxymethylfurfural with a recyclable V34@Fe3O4/C catalyst Enriched with Mixed-valence polyoxovanadate active centers - Chunhui Zhang; Mengqi Wang; Changhao Zhao; Junpeng Wang; Yundong Cao; Linlin Fan; Hong Liu; Guang-Gang Gao (Fuel, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Double synergistic strategy: mechanism of acetone sensing performance enhancement by Pt@Cu3(HHTP)2 derivatives modifying three-dimensional inverse opal In2O3 - Lanlan Guo; Jiaru Yang; Yuying Cai; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Advances in preclinical studies of ginsenoside Rh2 in antitumor therapy - Zheng Xu; Guanghuan Shen; Zhihua Xing; Jianghan Luo; Yu Zhu; Xuan Liu; ShiHao Li; Hao Wang; Linlin Cui (Medicinal Chemistry Research, 2025)

Embryonic and Larval Development of an Interspecific Grouper Backcross Between the Kelp Grouper (Epinephelus moara) ♀ and KGGG (E. moara ♀ × E. lanceolatus ♂) ♂ - Yidan Xu; Yongsheng Tian; Shihao Wang; Tangtang Ding; Linna Wang; Zhentong Li; Linlin Li; Yang Liu (Fishes, 2025)
Backcrossing serves as an effective tool for interspecific gene introgression, facilitating germplasm improvement. To develop superior grouper aquaculture varieties, in this study, a backcrossed breed was constructed by crossing a male hybrid grouper, KGGG (Epinephelus moara ♀ × E. lanceolatus ♂), with a female parent kelp grouper (KG; E. moara). Here, we observed embryonic, larval development, and morphological changes in KG × KGGG. Additionally, the total length and body weight of the backcrossed breed and maternal parent were compared at 160 d post hatching (dph). The results showed that fertilization and the hatching rate were 73.23 ± 4.23% and 51.74 ± 3.67%, respectively, and the egg size was 0.89 ± 0.03 mm. Hatching occurred 23:19 h after fertilization at 25 ± 1 °C, and the newly hatched larvae were 1.94 ± 0.13 mm in length. Furthermore, at 160 dph, the total length and body weight of the backcrossed breed were 1.2-fold and 1.9-fold greater, respectively, when compared with those of the maternal parent. Importantly, it is possible that backcrossed KG × KGGG could become a dominant strain in grouper aquaculture practices.

Characterization of TGFβ Signaling Components in Large Yellow Croaker (Larimichthys crocea) and Their Role in Growth and Body Shape Regulation - Xuyang Jiang; Lu Zhang; Xin Hu; Mingchao Cui; Jie Li; Huang Liu; Linlin Yao (Journal of Marine Science and Engineering, 2025)
The transforming growth factor β (TGFβ) signaling axis plays a pivotal role in orchestrating a wide array of biological functions, encompassing cellular growth, proliferation, and differentiation. The aim of the present study was to identify the members of TGFβ signaling pathway and their expression patterns in large yellow croaker (Larimichthys crocea) under different culture modes. TGFβ signaling pathway and their expression patterns in fish reared under two different culture modes: Group N (2400 fish in a 120 m3 cage) and Group V (168,000 fish in a 5600 m3 aquaculture vessel). After 120 days, we analyzed 15 fish from each group and found that Group V exhibited faster growth and a slender body shape compared to Group N. Bioinformatics analysis identified 48 TGFβ superfamily members in L. crocea, including 21 ligands, 10 receptors, and 3 Smads. mRNA expression levels indicated that these signaling molecules influence growth rate and body shape through five distinct ligand–receptor–R-Smad pathways, with the INHBB-, Nodal-, and GDF3-ACVR2A-ALK4-Smad2 axis playing a predominant role in regulating these traits.

OA-based photo-Fenton system generates oxidizing and reducing radicals for the simultaneous removal of 1-NA and Cr (VI) in surface waters - Linlin Liang; Li Sun; Qiuwen Wang; Fuqiang Zhang; Huixue Li; Guoquan Liu; Pengfei Wang; Sihui Zhan (Water Research, 2025)

Predicting and quantifying damage characteristics in mechanized harvesting: A collision-based study of apples - Zixu Chen; Linlin Sun; Linlong Jing; Xinpeng Cao; Yongxian Wang; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2025)

Integrated transcriptome and metabolome analyses reveal regulatory mechanisms governing carbohydrate biosynthesis in Panax ginseng - Qiao Jin; Qiuxia Wang; Linlin Zhang; Yue Zhang; Zhengbo Liu (Plant Science, 2025)

The regulation of gut microbiota and urate lowering: A study on the mechanisms of action of probiotics and plant components - Zhihua Xing; Yue Xu; Wen Jiang; Mingyu Gao; Guanghuan Shen; Yingjie Liu; Na Ling; Linlin Cui (PharmaNutrition, 2025)

Study on complex failure modes of super-long piles in deep-water and soft-clay seabed under multiple combined loads - Linlin He; Xuan Liu; Yuanshi Xie; Shuting Cao; Yue Liang; Yang Liu (Ocean Engineering, 2025)

Thermodynamic drivers of rice glutenin Assembly: Multiscale analysis of Hierarchical structure and intermolecular bonding - Wanshan Yang; Huining Zhang; Haoyu Li; Yuhan Jiang; Zhiqi Wang; Menglu Yang; Sitong Liu; Yinyuan He; Bing Wang; Linlin Liu; Yan Wang; Fenglian Chen; et al. (Journal of Cereal Science, 2025)

Simultaneous N-methyl pyrrolidone and total-nitrogen removals in a single aerobic process - Fei Liu; Meng Huang; Chenyu Li; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

In-situ phenolics enrichment of Camellia oleifera Abel oil via novel aqueous enzymatic extractions and its potential mechanism - Linlin Liu; Chengyu Jin; Yuanchao Lu; Ningxiang Yu; Xiaohua Nie; Qin Ye; Yuanxiang Jin; Xianghe Meng (Food Chemistry, 2025)

Seismic behavior of prefabricated-assembled frames with corrugated steel tube confined connections and piers: Experiments, numerical models, and design - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

Melanoidins induced transformation of protein and polysaccharide during thermal hydrolysis-pyrolysis of sludge via non-covalent forces - Yimeng Jiao; Yifei Wu; Ziyang Dong; Jinxuan Ning; Jialin Wang; Lu Liu; Zhengda Lin; Yu Tian; Linlin Yin; Jun Zhang (Chemical Engineering Journal, 2025)

Constructing artificial interphase layer of polyoxovanadates with high oxidizability and reversibility to boost dendrite-free lithium metal anode - Yihai Song; Jiayuan Zhang; Chunhui Zhang; Linlin Fan; Jian Song; Yundong Cao; Yi Feng; Hong Liu; Guanggang Gao (Chemical Engineering Journal, 2025)

A coupled model of surface water-groundwater interaction with the effect of riverbed deformation in the alluvial channel - Linlin Li; Hang Li; Genguang Zhang; Defu Liu; Yao Xiao; Ying Liu; Jiahao Zou (CATENA, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

Effects of Land-Use Change on Soil Infiltrability and Preferential Flow in Typical Low Hilly Area - Linlin Chu; Rong Ma; Yue Liu; Yan Zhao; Lidong Bi; Chen Dan (Journal of Soil Science and Plant Nutrition, 2025)

Smartphone-assisted portable electrochemical sensing platform for point-of-care detection of thiocyanate using a laser-induced graphene composite electrode - Xiaoming Yuan; Linlin Chen; Ruwei Liu; Shilin Li; Xiu-wen Wu; Yunhan Ling (Analytica Chimica Acta, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Interpretability and identification of dimorphism in morphological indexes of Larimichthys crocea based on machine learning models - Liguo Ou; Linlin Lu; Weiguo Qian; Bilin Liu (Fisheries Research, 2025)

Norgestrel shows androgenic properties and triggers reproductive neuroendocrine toxicity in the testes of Pacific oysters (Crassostrea gigas) - Yan Fang; Baojun Liu; Juan Wang; Haoyang Zhong; Linlin Fan; Yuchao Huang; Changkun Chen; Songtao Lu; Tao Zheng (Journal of Hazardous Materials, 2025)

High-pressure homogenization treatment on yeast protein: Effect on structure and emulsifying properties - Zihuan Wang; Xiuli Xu; Zhaoli Liu; Tong Xu; Linlin Ma; Fuhang Song (Food Research International, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Preclinical models in the study of lymph node metastasis - Liya Wei; Zizhan Li; Niannian Zhong; Leiming Cao; Guangrui Wang; Yao Xiao; Bo Cai; Bing Liu; Linlin Bu (Journal of Zhejiang University-SCIENCE B, 2025)

circ_0000554 promotes macrophage M2 polarization mediated by glycolytic reprogramming and aggravates COPD injury - Yamei Song; SiQin Han; Linlin Liu; Lifeng Zheng; Jing Wang; Zhaobo Cui; Xixin Yan (Toxicology Letters, 2025)

Dissolved organic matter (DOM) – Driven variations of cadmium mobility and bioavailability in waterlogged paddy soil - Mingming Tao; Xianlin Ke; Jingnan Ma; Linlin Liu; Yanhua Qiu; Zhengyi Hu; Fulai Liu (Journal of Hazardous Materials, 2025)

Synergistic effects on microstructural, rheological and functional properties of starch-enhanced processed mozzarella cheese - Linlin Tang; Jialin Liu; Ke Li; Yumeng Zhang; Shaomeng Luan; Tietao Chen; Hongjuan Li; Jinghua Yu (Food Structure, 2025)

Cobalt-doped covalent organic framework effectively enhances Fenton-like activity: radical and non-radical dual pathways enhancement - Yunchao Ma; Chuanxue You; Yuxin Yao; Shengnan Qi; Tianyu Zhou; Wei Jiang; Keyu Cui; Bo Hu; Linlin Liu (Chemical Engineering Journal, 2025)

The Physiological and Flavonoid Metabolism of the Tea Plant in Response to Nitrogen Nutrition is Regulated by the Ultraviolet-B Radiation Environment - Fang Dong; Hua Zhang; Linlin Liu; Jianyun Ruan; Meiya Liu; Qunfeng Zhang (Journal of Plant Growth Regulation, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

One-step narrow-thermal-cycling strand exchange amplification for sensitive detection of porcine reproductive and respiratory syndrome virus - Linlin Zhuang; Chunlei Song; Li Sun; Haiqiang Xie; Liqun Wang; Qingxin Liu; Hongjing Shi; Jianbo Yang; Qiuping Shen (Archives of Microbiology, 2025)

Insight into peroxidase-mediated Pinus massoniana resin browning, and browning inhibition strategy - Hanxiao Liu; Xiaopeng Chen; Dandan Yu; Siheng Zhang; Jiezhen Liang; Xin Li; Xiaojie Wei; Linlin Wang (Sustainable Chemistry and Pharmacy, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Study on the characteristics of an underwater vehicle pump-jet propeller under the influence of drag-reduction air - Xuanhao Shao; Jianwei Zhang; Haopeng Cai; Penglei Chen; Heng Liu; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2025)

Explicit dynamics simulation study to determine the damage patterns of apples (Red Fuji) under impact loading - Zixu Chen; Linlin Sun; Linlong Jing; Yi Liu; Jingwei Sun; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Journal of Stored Products Research, 2025)

Promoting oxidation of high concentration CO via strong metal support interaction in unreduced Pt-based catalysts - Yulong Yang; Xiaokun Yi; Linlin Deng; Zitong Zhao; Zimu Liu; Mingtai Li; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Construction of Fenton-like systems based on hierarchical nanoconfinement for efficient antibiotic removal - Linlin Su; Wei Hu; Xiaolun He; Chao Chen; Min Xu; Xiaoyu Yu; Yan Liu; Gang Yang; Lulu Long (Journal of Environmental Chemical Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

The roles of Paracoccus huijuniae for enhancing denitrification with N-methyl pyrrolidone as the electron donor - Meng Huang; Songyun Chen; Fei Liu; Haiyun Zhang; Xiaobing Gao; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

Ginsenoside Rk1 Ameliorates Non-Alcoholic Fatty Liver Disease by Targeting CD36 to Modulate the AMPK Signaling Pathway - Yuqing Wu; Zhiguang Duan; Linlin Qu; Yannan Liu; Xiaoxuan Ma; Daidi Fan (Food Research International, 2025)

Lacticaseibacillus paracasei SB27 enhances its gastrointestinal tolerance, adhesion and colonization by producing biofilm - Yinxue Liu; Linlin Hao; Yisuo Liu; Lu Jiang; Huaxi Yi (Food Bioscience, 2025)

Quantitative proteomic analysis reveals target proteins of benzyl isothiocyanate against multidrug-resistant Staphylococcus aureus - Xujia Ming; Hongbo Li; Na Li; Zhenbin Liu; Linlin Zhu; Haizhen Mo; Liangbin Hu (Food Bioscience, 2025)

Screening of hypoglycemic and probiotic properties of Pediococcus acidilactici FM-Pa-JXM94 and exploring the potential hypoglycemic mechanism - Ying Wang; Hui Zhang; Xingna Wang; Yu Zhang; Linlin Fan; Yanhong Ma; Xiaoli Liu (Food Bioscience, 2025)

Enhanced viability of Lactiplantibacillus plantarun by encapsulation with whey protein isolate fibrils and polysaccharides through layer-by-layer coating - Siyuan Li; Wei Su; Yu Zhang; Wanling Gan; Xiaoli Liu; Linlin Fan (Food Hydrocolloids, 2025)

Glycyrrhizic acid alleviates gefitinib-induced liver injury by regulating the p53/p21 pathway and releasing cell cycle arrest - Min Li; Shuaijun Peng; Jingjing Bu; Siqi Quan; Liming Liu; Zhouli Yue; Linlin Wang; Yucheng Li (Food and Chemical Toxicology, 2025)

Nitrogen-rich carbon nitride activated peroxymonosulfate for the efficient photodegradation of 2, 4-dichlorophenol: Performance and mechanism insight - Tianyu Zhou; Siyi Wang; Meng Tai; Juan Du; Dongshu Sun; Guangbo Che; Linlin Liu; Chunhong Ma; Bo Hu (Environmental Research, 2025)

Performance and mechanism of tris(2-chloropropyl) phosphate (TCPP) removal in an iron-carbon microelectrolysis constructed wetland system - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Chemical Engineering Journal, 2025)

Tendon injury repair strategy driven by supramolecular hydrogen bonding and dynamic covalent bond self-assembly microspheres - Taishan Liu; Xiaoxuan Ma; Chenhui Zhu; Yu Mi; Jing Zhao; Linlin Qu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Polysaccharides from traditional Chinese medicine and their nano-formulated delivery systems for cancer immunotherapy - Linlin Sun; Yuting Liu; Qihui Sun; Guimei Wang; Baoxiang Du; Bodong Liu; Tian Gao; Pan Zhao; Yong Yang; Rong Rong (Carbohydrate Polymers, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Nine-year biochar history increases topsoil nitrogen stocks and reduces the refractory organic nitrogen fractions in deep soils - Di Wang; Shuai Liu; Liwei Hao; Qi Yue; Linlin Jiang; Yu Lan; Wenfu Chen (Journal of Soils and Sediments, 2025)

Prediction of landfill gases concentration based on Grey Wolf Optimization – Support Vector Regression during landfill excavation process - Zhansheng Liu; Zehua Zhang; Qingwen Zhang; Linlin Zhao (Waste Management, 2025)

Protective effects of resveratrol on honeybee health: Mitigating pesticide-induced oxidative stress and enhancing detoxification - Linlin Liu; Min Shi; Yanyan Wu; Jiali Hao; Junxiu Guo; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2025)

Reaction mechanism of extracting Li and Fe from retired lithium iron phosphate battery powder through roasting and water leaching with sulfamic acid - Zhenning Liu; Zhenan Jin; Linlin Tong; Shuo An; Tenghao Yang (Journal of Cleaner Production, 2025)

Planning conservation priority areas for marine mammals accounting for human impact, climate change and multidimensionality of biodiversity - Linjie Li; Yanli Tang; Hao Dong; Linlin Zhao; Changdong Liu (Journal of Environmental Management, 2025)

Impact of freeze-thaw cycles on the structural and quality characteristics of soy protein gels with different 11S/7S protein ratios - Qinlin Hu; Lidan Qiu; Ying Zhu; Yuyang Huang; Linlin Liu; Tianlu Han; YiHan Song; Xiuqing Zhu (Food Chemistry, 2025)

The influence of different drying methods on the molecular structure and digestive resistance of type 3 resistant starch (RS3) - Qing Su; Linlin Sun; Lirong Chen; Xingya Wang; Kaichang Liu; Kuijie Gong (Food Chemistry, 2025)

Polystyrene microplastics (PS-MPs) harness copper presence and promote impairments in early zebrafish (Danio rerio) larvae: Developmental, biochemical, transcriptomic approaches and nontargeted metabolomics approaches - Liqiao Zhang; Dongqiu Guo; Xinrui Dong; Longxiao Liu; Mengqi Jiang; Linlin Song; Xia Wang (Environmental Research, 2025)

Spatiotemporal variations of dissolved nitrous oxide concentrations in small water bodies in a typical urban landscape in eastern China - Xuebing Chen; Yuye Shen; Yihong Liu; Fangfang Zhang; Linlin Tian; Jing Wang; Yanjiang Cai; Yan Li; Scott X. Chang (Environmental Pollution, 2025)

Huge challenges of improving ozone pollution in China: High regional background ozone concentrations calculated from observational data - Yusi Liu; Yang Zhang; Fan Yang; Linlin Liang; Guiqian Tang (Environmental Pollution, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

Effective remediation of benzo [a] anthracene contaminated soil by combination of low-temperature thermal desorption and advanced oxidation - Yangyang Ma; Chiquan He; Linlin Yang; Xiaoyan Liu; Feifei Wang (Chemical Engineering Journal, 2025)

The influence of 2,6-Di-tert-butyl-p-cresol stress on the microalga Phaeodactylum tricornutum and phycosphere bacteria community - Xiao Lu; Jie Liu; Xinfeng Xiao; Jianliang Xue; Dongle Cheng; Linlin Zhang (World Journal of Microbiology and Biotechnology, 2025)

Source identification of polycyclic aromatic hydrocarbons (PAHs) in river sediments within a hilly agricultural watershed of Southwestern China: an integrated study based on Pb isotopes and PMF method - Fen Xu; Chunmei Jiang; Qiang Liu; Rui Yang; Weiwei Li; Yao Wei; Linlin Bao; Hongjin Tong (Environmental Geochemistry and Health, 2025)

Physical contraction strategy for large-scale fabrication of reduced graphene oxide-coated solid phase microextraction fibers - Linlin Wei; Jianyun Sun; Xingguo Wang; Ting Qi; Aiying Song; Rong Liu; Xinghe He (Analytica Chimica Acta, 2025)

Transcranial Magnetic Stimulation Alleviates Spatial Learning and Memory Impairment by Inhibiting the Expression of SARM1 in Rats with Cerebral Ischemia–Reperfusion Injury - Linlin Jiang; Yule Wang; Yingxi He; Ying Wang; Hao Liu; Yu Chen; Jingxi Ma; Ying Yin; Lingchuan Niu (NeuroMolecular Medicine, 2025)

Application of artificial intelligence in fish information identification: a scientometric perspective - Liguo Ou; Linlin Lu; Weiguo Qian; Bilin Liu (Frontiers in Marine Science, 2025)
In the context of the growing demand for the sustainable development and conservation of fish stocks, artificial intelligence (AI) technologies are essential for supporting scientific fish stock management. Artificial intelligence technology provides an effective solution for the intelligent recognition of fish information. This study used bibliometric analysis to review a sample of 719 scientific articles from the WoSCC (Web of Science Core Collection) database from 2014-2024. The results revealed a significant increase in the number of publications from 2014-2024, with publications mainly from China, the USA (the United States) and other developed countries. The top three impactful journals are Ecological Informatics, Computers and Electronics in Agriculture and the ICES Journal of Marine Science. The most frequent keyword co-occurrence analysis was deep learning, and the best keyword clustering effect was computer vision. The findings indicate that this bibliometric evaluation provides a holistic visualization of the research frontier of AI in fish information identification, and our findings underscore the growing global importance of AI in fish information identification research and highlight publication trends, hotspots, and future research directions in this area. In conclusion, our findings provide valuable insights into the emerging frontiers of AI-based fish information identification.

Seasonal and spatial distribution of AmphiOctopus fangsiao and Octopus variabilis in the southern Yellow and East China Seas: Fisheries management implications based on climate scenario predictions - Linlin Yang; Min Xu; Zunlei Liu; Yi Zhang; Yan Cui; Shengfa Li (Regional Studies in Marine Science, 2025)

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

Understanding the effect and mechanism of ε-polylysine on the improvement of tofu storage quality via biofilm inhibition by Bacillus licheniformis and Bacillus amyloliquefaciens - Jingbo Kang; Xin Zhang; Yuyang Huang; Ying Zhu; Linlin Liu; Bingyu Sun; Min Qu; Xiuqing Zhu (Food Bioscience, 2025)

Correlation between the physicochemical and bacteriological qualities of pickled chili pepper (Paojiao) and its nitrite degradation study - Jianhui Wang; Miao Liu; Linlin Ye; Xiaoyi Hou; Zhenyu Li; Linzhi Tang; Na Deng; Hui Li (Food Bioscience, 2025)

Modeling of sediment exchange process and channel evolution in the downstream reach below the Three Gorges Dam - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Defu Liu; Hang Li; Yu Lei (CATENA, 2025)

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

Association of Urinary Phthalate Metabolites with Lipid Profiles and the Mediating Role of Serum Globulin: A Repeated-Measures Study - Kun Huang; Linlin Liu; Lei Zhao; Miao Liu; Chongjian Wang; Wenting Guo; Huihua Yang; Rui Zhu; Xiaomin Zhang (Exposure and Health, 2025)

Seasonal spatial distribution patterns of AmphiOctopus ovulum in the East China Sea: current status future projections under various climate change scenarios - Linlin Yang; Min Xu; Yan Cui; Shuhao Liu (Frontiers in Marine Science, 2025)
Currently, there is also little up to date information on the the current population status and life history traits of AmphiOctopus ovulum , a very often seen cephalopod species in the East China Sea. It is therefore important to figure out the seasonal spatial distribution of this species, both in terms of number and biomass, and the environmental variables which determine them. Additionally, climate change plays an important role in determining the characteristics of individual species and thus on the ecosystems they inhabit. We set out to understand the responses of A. ovulum to habitat variables and to make projections based on the climate change scenarios described in the IPCC’s SSP1-2.6 and SSP5-8.5 criteria. We carried out seasonal bottom trawling surveys in the East China Sea region during 2018 and 2019 to fill this knowledge gap. Our results showed that the average individual size values ranged from 17.80−43.00 g·ind -1 in spring and 23.49−33.00 g·ind -1 in summer; the measured sea bottom temperature, sea bottom salinity, and depth value ranges were 10.81−27.06°C, 31.73–35.25‰, and 91–103 m independently in spring to winter. Our study showed that A. ovulum was distributed in the area between 27°–29°N, 122.5°–125°E during spring to autumn, and expanded into the area between 26.5°–32.5°N, 121°–124.5°E in winter. The core habitat of A. ovulum was centered on the area between 27.5°–28°N, 122.5°–123.5°E, and can be expected to expand to the northeast and southwest independently under the most likely global warming scenarios. Our results will benefit the development of suitable conservation measures for cephalopod habitats, and incorporate the impacts of climate change into fisheries management programs.

Current and future thermal effects and spatial optimization modelling of urban greenspace in megacity - Rundong Feng; Shenghe Liu; Fuyuan Wang; Bin Chen; Kaiyong Wang; Linlin Xu (Sustainable Cities and Society, 2025)

Identification and characterization of ClAPRR2, a key candidate gene controlling watermelon stripe color - Shuang Liang; Miaomiao Yang; Linlin Zhang; Xufeng Fang; Xian Zhang; Chunhua Wei; Zuyun Dai; Zhongzhou Yang; Chaonan Wang; Bin Liu; Feishi Luan; Shi Liu (Plant Science, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

Enhancement of farinographic characteristics of rice dough and rice bread quality with combined chemical and enzymatic approaches - Huining Zhang; Wanshan Yang; Yuhan Jiang; Haoyu Li; Menglu Yang; Zhiqi Wang; Bing Wang; Linlin Liu; Hongchen Fan; Fenglian Chen; Ying Liu (Food Bioscience, 2025)

Effect of freezing-thawing treatment on the quality and structure of soymilk gels induced by different coagulants - Ying Zhu; Wenhua Lei; Lidan Qiu; Simiao Liu; Ruqi Guo; Yuyang Huang; Linlin Liu; Mingshou Lv; Bingyu Sun; Min Qu; Ying Sun; Xiuqing Zhu (Food Hydrocolloids, 2025)

Fabrication and characterization of gelatin/carboxymethyl chitosan composite film incorporated with carvacrol and its preservation efficacy in Chinese mitten crab (Eriocheir sinensis) - Anthony Pius Bassey; Xiaozhen Cui; Isaiah Henry Ibeogu; Fan Wang; Mustapha Muhammad Nasiru; Hadiza Kabir Bako; Linlin Fan; Xiaoli Liu (Food Hydrocolloids, 2025)

Bacterial community composition and metabolic characteristics of three representative marine areas in northern China - Huameng Ge; Chengcheng Li; Conghui Huang; Linlin Zhao; Bailin Cong; Shenghao Liu (Marine Environmental Research, 2025)

The role of telomere shortening in ambient ozone exposure-related insulin resistance - Ruiying Li; Gongbo Chen; Wei Liao; Yinghao Yuchi; Xiaohuan Yang; Ziyuan Zhang; Xiaotian Liu; Zhenxing Mao; Linlin Li; Jiahui Zhao; Huijun Li; Wenqian Huo; et al. (Journal of Hazardous Materials, 2025)

Improvement of 3D printing and subsequent microwave freeze-drying solidification accuracy of pineapple gel-based inks: Infill percentage control and internal models design - Yunfei Bao; Wenchao Liu; Linlin Li; Guangyue Ren; Chung Lim Law; Weiwei Cao; Jiayao Wang; Zhenjiang Luo; Junliang Chen; Xu Duan (Journal of Food Engineering, 2025)

Failure and post-failure kinematic disaster processes of columnar rock masses based on 3D discontinuous deformation analysis - Ke Ma; Shengze Zhao; Guoyang Liu; Jianbin Miao; Jiashuo Kang; Linlin Wang; Qun Yu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Effect of freeze-thaw cycles on the quality of Yuba with different protein-lipid ratios on its protein-lipid network system - Lidan Qiu; Ying Zhu; Xiuqing Zhu; Linlin Liu; Mingshou Lv; Yuyang Huang; Bingyu Sun; Min Qu (Food Chemistry, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

Lactic acid bacteria in relieving constipation: mechanism, clinical application, challenge, and opportunity - Tong Zhang; Wenxu Liu; Huimin Lu; Ting Cheng; Linlin Wang; Gang Wang; Hao Zhang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2025)

Contribution of mitochondria to postmortem muscle tenderization: a review - Feng Huang; Zhenjiang Ding; Jinsong Chen; Bing Guo; Linlin Wang; Chunmei Liu; Chunhui Zhang (Critical Reviews in Food Science and Nutrition, 2025)

A comprehensive review on iron‒carbon microelectrolysis constructed wetlands: Efficiency, mechanism and prospects - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Water Research, 2025)

A non-isothermal kinetic study on the extraction of metals from spent lithium iron phosphate batteries using the NH2SO3H roasting process - Zhenning Liu; Zhenan Jin; Linlin Tong; Jiangping Huang; Tenghao Yang (Process Safety and Environmental Protection, 2025)

Global distribution pattern and conservation of the cosmopolitan cold-water coral species Desmophyllum dianthus under climate change - Wenhao Huang; Zongling Wang; Fangyuan Qu; Chang Zhao; Miaozhuang Zheng; Zhaohui Zhang; Shenghao Liu; Qinzeng Xu; Xuelei Zhang; Linlin Zhao (Journal of Environmental Management, 2025)

2D manganese-doped calcium carbonate nanosheets as activable MRI/US imaging Guided enhanced calcium influx for Boosted regulatory cell death - Mingya Tan; Linlin Huo; Jie Zeng; Shiqi Zhu; Jianfeng Bao; Mengke Fan; Jiangyang Li; Meiling Liu; Jiayi Zhao; Zhenghuan Zhao (Chemical Engineering Journal, 2025)

Algae-inspired chitosan-pullulan-based multifunctional hydrogel for enhanced wound healing - Taishan Liu; Huan Lei; Linlin Qu; Chenhui Zhu; Xiaoxuan Ma; Daidi Fan (Carbohydrate Polymers, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

Threshold of sediment incipient motion on a three-dimensional riverbed by considering the hiding-exposure effect with experimental investigations - Linlin Li; Yao Xiao; Genguang Zhang; Yu Lei; Hang Li; Defu Liu (Acta Geophysica, 2024)

Impact of chlorantraniliprole on honey bees: Differential sensitivity and biological responses in Apis mellifera and Apis cerana - Wenmin Li; Yikun Zan; Tong Wu; Sa Yang; Linlin Liu; Shanshan Li; Pingli Dai; Jing Gao (Science of The Total Environment, 2024)

N18 ring: A building block for constructing 1D and 2D polymeric nitrogen frameworks - Yuxiang Gao; Ying Zhang; Shuang Liu; Bo Jin; Linlin Guo; Xu Guo; Zhen Yao; Peng Wang; Bingbing Liu (Science Bulletin, 2024)

The mediating role of abnormal ZEB1 methylation in the association between nickel exposure and non-syndromic orofacial cleft - Yongyan Chen; Yaquan Pan; Lijun Liu; Yingnan Guo; Lei Jin; Aiguo Ren; Linlin Wang (Reproductive Toxicology, 2024)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

The complete genome sequence of Streptomyces sp. FIM 95-F1, a marine actinomycete that produces the antifungal antibiotic scopafungin - Peng Fei; Lin Yangjun; Zhuang Yuee; Lin Ping; Liu Chengzhi; Chen Linlin; Jiang Hong; Lian Yunyang; Zhang Wenzhou; Huang Youxia (Marine Genomics, 2024)

Electronic structure regulation of Cu-based Ruddlesden-Popper perovskites by cobalt doping for enhanced degradation of oilfield fracturing wastewater in electrocatalytic peroxymonosulfate system - Xin Liu; Jingyang Li; Yuexiang Li; Jian Fu; Chengzhi Liu; Linlin Yang (Journal of Environmental Chemical Engineering, 2024)

Roles of mTOR-p70S6K signaling pathway and HO-1 in ethylbenzene-induced hepatoxic effects in L02 cells - Siyu Liu; Linlin Chen; Hui Peng; Qiang Zhang; Qiang Zeng; Bo Cui; Ming Zhang (Food and Chemical Toxicology, 2024)

Prenatal co-exposure to phthalate metabolites and bisphenols among non-syndromic cleft lip and/or palate in offspring - Sainan Li; Haiyan Zhu; Chen Yang; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

Precise fabrication and superior combustion properties of n-B pomegranate microspheres based on a new dissolution-dispersion-coating method - Yushu Xiong; Baoxuan Li; Yinghong Wang; Linlin Liu; Jie Huang; Suhang Chen; Fengqi Zhao; Kangzhen Xu (Chemical Engineering Journal, 2024)

LncRNA018392 promotes the proliferation of Liaoning cashmere goat skin fibroblasts by upregulating CSF1R through binding to SPI1 - Mei Jin; Weiyu Fan; Suhe Lv; Tianwei Xue; Linlin Cong; Xinyang Liu; Lixin Cui (Molecular Biology Reports, 2024)

A multiscale dilated attention network for hyperspectral image classification - Chao Tu; Wanjun Liu; Wentao Jiang; Linlin Zhao; Tinghao Yan (Advances in Space Research, 2024)

Genes and Pathways Underpinning Klinefelter Syndrome at Bulk and Single-Cell Levels - Linlin Tian; Yan Yu; Ziqing Mao; Dandan Xu; Hongbo Zhang; Mengkai Qiao; Tong Chen; Wen Liu (Biochemical Genetics, 2024)

Comparative analysis of climate-induced habitat shift of economically significant species with diverse ecological preferences in the Northwest Pacific - Wanchuan Dong; Xinlu Bai; Linlin Zhao; Hao Dong; Changdong Liu (Frontiers in Marine Science, 2024)
The Northwest Pacific Ocean is the most productive fishing ground in the Pacific Ocean, with a continuous rise in water temperature since 1990. We developed stacked species distribution models (SSDMs) to estimate the impacts of climate change on the distribution dynamics of economically significant species under three climate change scenarios for the periods 2040-2060 and 2080-2100. Overall, water temperature is the most important factor in shaping the distribution patterns of species, followed by water depth. The predictive results indicate that all the species show a northward migration in the future, and the migration distance varies greatly among species. Most pelagic species will expand their habitats under climate change, implying their stronger adaptability than benthic species. Tropical fishes are more adaptable to climate change than species in other climate zones. Though limitations existed, our study provided baseline information for designing a climate-adaptive, dynamic fishery management strategy for maintaining sustainable fisheries.

Evaluation of Tembusu virus single-round infectious particle as vaccine vector in chickens - Yunzhen Huang; Zhe Liu; Junqin Zhang; Jiawen Dong; Linlin Li; Yong Xiang; Ruihuan Kuang; Shimin Gao; Minhua Sun; Yongjie Liu (Veterinary Microbiology, 2024)

Greenspace coverage vs. enhanced vegetation index: Correlations with surface urban heat island intensity in different climate zones - Linlin Liu; Bohong Zheng (Urban Climate, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Estimating global 0.1° scale gridded anthropogenic CO2 emissions using TROPOMI NO2 and a data-driven method - Yucong Zhang; Shanshan Du; Linlin Guan; Xiaoyu Chen; Liping Lei; Liangyun Liu (Science of The Total Environment, 2024)

Exosomal miR-129-2-3p promotes airway epithelial barrier disruption in PM2.5-aggravated asthma - Caihong Wang; Zeyu Niu; Yan Zhang; Nannan Liu; Xiaotong Ji; Jiayu Tian; Linlin Guan; Dongxing Shi; Huiqiu Zheng; Yuhui Gao; Lifang Zhao; Wenping Zhang; et al. (Journal of Environmental Management, 2024)

Decreased formulation pH and protein preheating treatment enhance the interaction, storage stability, and bioaccessibility of caseinate-bound lutein/zeaxanthin - Gang Zhang; Linlin He; Xin Qi; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhuang Ding; Zhengping Wang; Sangeeta Prakash (Food Research International, 2024)

Augmenting corn starch gel printability for architectural 3D modeling for customized food - Dongni Xian; Linlin Wu; Keying Lin; Peng Liu; Silin Wu; Yang Yuan; Fengwei Xie (Food Hydrocolloids, 2024)

Construction of covalent electrode/solid electrolyte interface for stable flexible solid-state lithium batteries - Junlong Zou; Linlin Wang; Jun Zhang; Qiyue Sun; Yongyin Wang; Mingtao Zheng; Yong Xiao; Hang Hu; Yingliang Liu; Yeru Liang (Chemical Engineering Journal, 2024)

Tailoring carbon intercalated α,β-FePc heterophase junction to boost electron transfer for 1O2-dominated photo-Fenton reaction - Zhiling Du; Cailiang Yue; Linlin Zhu; Changqing Zhu; Qing Du; Fuqiang Liu (Chemical Engineering Journal, 2024)

High-value multilayer graphene oxide prepared by catalytic pyrolysis of petroleum tar and applications: Trash to treasure - Lu Liu; Jialin Wang; Yifei Wu; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemical Engineering Journal, 2024)

Insights into the uptake, accumulation, and metabolism of UV-328 in lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.) - Bingru Li; Zhenzhen Yao; Qi Liu; Linlin Guo; Zhihong Ma; Cheng Li (Chemosphere, 2024)

Transcriptomic analysis uncovers a biphasic response to precocious Eimeria acervulina infection in chicken duodenal tissue - Ning Zhang; Jie Liu; Yuanyuan Zhang; Linlin Chen; Sixin Zhang; Xianyong Liu; Xinming Tang; Xiaolong Gu; Shiyi Chen; Xun Suo (Veterinary Parasitology, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Biomass-derived carbon dots with pharmacological activity for biomedicine: Recent advances and future perspectives - Yue Liu; Linlin Zhang; Huijuan Cai; Xiaoli Qu; Junbiao Chang; Geoffrey I.N. Waterhouse; Siyu Lu (Science Bulletin, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

Iron-nitrogen coupling mediates soil microbial community composition and gene expression during the formation of rusty root in Panax ginseng from three northeast provinces in China - Qiao Jin; Linlin Zhang; Keming Cao; Xiaoxi Pan; Zhengbo Liu; Yiming Guan; Xiangxi Zuo; Yayu Zhang; Qiuxia Wang (Journal of Environmental Chemical Engineering, 2024)

3D-printed devices for continuous-flow lithium recovery of brines - Jiangtao Yu; Jie Zhu; Zhuo Han; Peng Cui; Haiying Mi; Anan Zhang; Linlin Chen; Xiaowei Li; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2024)

Source characteristics of the 2006 Pingtung earthquake doublet off southern Taiwan and the possible contribution of submarine landslides to the Tsunami - Gui Hu; Linlin Li; Kenji Satake; Tso-Ren Wu; Peitao Wang; D.J. Doong; Philip L.-F. Liu (Earth and Planetary Science Letters, 2024)

Functional molecules surface segregation engineering in electrospinning: Design, regulation, and applications - Linlin Cao; Chen Qu; Jingchong Liu; Wenhui Li; Lihua Jiang; Boyu Jing; Chuandong Wu; Jiemin Liu (Chemical Engineering Journal, 2024)

Contribution of the TGFβ signaling pathway to growth of Pacific oyster (Crassostrea gigas) - Linlin Yao; Yumeng Liu; Li Li; Xuyang Jiang (Aquaculture, 2024)

The recent high occurrence of spring atmospheric droughts over central Hengduan Mountains is unprecedented in 669-year tree-ring records - Linlin Cui; Jinjian Li; Wenling An; Ningsheng Qin; Huiming Song; Yu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Water-dependent effects of biodegradable microplastics on arsenic fractionation in soil: Insights from enzyme degradation and synchrotron-based X-ray analysis - Kailin Gong; Tianzi Liu; Cheng Peng; Ziyi Zhao; Xiang Xu; Xuechun Shao; Xuan Zhao; Linlin Qiu; Wenwen Xie; Qian Sui; Wei Zhang (Journal of Hazardous Materials, 2024)

Interaction characteristics and mechanism of Cr(VI)/Cr(III) with microplastics: Influence factor experiment and DFT calculation - Linlin Ma; Tong Liu; Jiaxin Li; Qing Yang (Journal of Hazardous Materials, 2024)

A multi-omics-based investigation into the regulation of phenolics in fresh maize kernels at different developmental stages - Xiaomin Tian; Di Han; Linlin Sun; Yuqiu Guo; Kaichang Liu; Lirong Chen; Kuijie Gong (Journal of Cereal Science, 2024)

Investigation on the exopolysaccharide production from blueberry juice fermented with lactic acid bacteria: Optimization, fermentation characteristics and Vis-NIR spectral model - Suqun Yang; Yang Tao; Xiayidan Maimaiti; Wei Su; Xiaoli Liu; Jianzhong Zhou; Linlin Fan (Food Chemistry, 2024)

Fabrication of polysaccharide-coated oleanolic acid-curcumin-coassembled nanoparticles (OA/Cur NPs): Enhancement of colloidal stability and water solubility - Linlin Yan; Han Liu; Yuhui Wang; Lulu Zhang; Chao Ma; A.M. Abd El-Aty (Food Chemistry, 2024)

Long-term non-flooded cultivation with straw return maintains rice yield by increasing soil pH and soil quality in acidic soil - Jingjie Zhou; Sheng Tang; Wankun Pan; Xiu Liu; Kefeng Han; Linlin Si; Qingxu Ma; Xiali Mao; Haoran Fu; Lianghuan Wu (European Journal of Agronomy, 2024)

Boosting TNBC immune checkpoint blockade with an imaging-therapy coupled ozone delivery nano system - Linlin Song; Zhihui Liu; Xiujing He; Tianyue Xu; Meixu Chen; Zihan Xu; Haina Zhao; Jiaojiao Suo; Hong Wang; Zhankun Yang; Shenglan You; Xiaoting Chen; et al. (Chemical Engineering Journal, 2024)

High-amylose starch-based gel as green adhesive for plywood: Adhesive property, water-resistance, and flame-retardancy - Yaoxing Chen; Yongjing Rao; Peng Liu; Linlin Wu; Guojie Zhang; Jianguo Zhang; Fengwei Xie (Carbohydrate Polymers, 2024)

Anti-cancer effects of nitazoxanide in epithelial ovarian cancer in-vitro and in-vivo - Xiangqun Yang; Zhenyan Liu; Xin Wang; Wenda Tian; Taoyu Zhao; Qiaoling Yang; Wenliang Li; Linlin Yang; Hongying Yang; Yue Jia (Chemico-Biological Interactions, 2024)

From trajectories to network: Delineating the spatial pattern of recreational walking in Guangzhou - Haochen Shi; Linlin Yao; Qiqi Liu; Yankai Wang; Zongcai Wei; Miaoxi Zhao; Ding Ma (Applied Geography, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

Exploring biomass addition in methanol production: A life cycle analysis of efficiency and environmental impacts - Linlin Liu; Shenghui Li; Yu Zhuang; Jian Du (Journal of Cleaner Production, 2024)

An integrated investigation combining network pharmacology and computer simulation dissects the potential mechanism of anti-obesity of Monascus pigments (MPs) - Jiaxing Li; Huijing Zhang; Linlin Xu; Huiqian Liu; Chenchen Qi; Chengtao Wang; Wei Chen (Food Bioscience, 2024)

Elevated [CO2] reduces CH4 emissions from rice paddies under in situ straw incorporation - Ting Bao; Ling Wang; Yuanfa Huang; Huixin Li; Lanying Qiu; Jiujie Liu; Linlin Shi; Yunlong Liu; Haoyu Qian; Yanfeng Ding; Yu Jiang (Agriculture, Ecosystems & Environment, 2024)

Low energy-consumption oriented membrane fouling control strategy in anaerobic fluidized membrane bioreactor - Lu Liu; Ze Guo; Yihe Wang; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

Variation characteristics of fluorescent biological aerosol particles in Beijing under springtime clean, haze and dusty condition - Linlin Liang; Wanyun Xu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Yangmei Zhang; Junying Sun (Urban Climate, 2024)

Integrative proteomic-metabolomics strategy reveals the regulators and mechanism of enhancing cyclic lipopeptides in the high-cell-density fermentation of Bacillus subtilis S1702 - Bo Zhang; Linlin Xu; Hui Yang; Zhengjun Pang; Wenshuo Zhang; Fenghuan Wang; Huilin Liu; Junfeng Fan; Bolin Zhang (Process Safety and Environmental Protection, 2024)

Provenance signature and tectono–sedimentary setting of the Permian Shihezi formation (Ordos basin, China): Insights from geochemistry and detrital zircon U–Pb dating - Shuyue Zhu; Lei Liu; Linlin Wang; Zhiwei Wang; Jianling Hu; Jingqi Zhang; Chenggong Zhang; Junxing Zhao; Hongde Chen (Marine and Petroleum Geology, 2024)

An evaluation on the shrinkage deformation characteristics of Chinese yam during multiphase microwave drying based on digital image processing - Mengmeng Yang; Linlin Li; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Ke Gao; Chung Lim Law; Xu Duan (Innovative Food Science & Emerging Technologies, 2024)

Fabrication of stable spherical soybean lipophilic protein nanogel for curcumin delivery: Carbony oxygen and aromatic ring flexibility binding to the beta−barrel - Jianhua Zeng; Junzhe Zou; Lanwei Zhang; Jinlong Zhao; Linlin Liu; Gen Lu; Bingyu Sun; Yanguo Shi; Xiuqing Zhu; Pimin Gong (Food Structure, 2024)

Chromium levels in placental tissue and neural tube defects: Association and mechanistic study - Yongyan Chen; Yingnan Guo; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

PCDH11X mutation as a potential biomarker for immune checkpoint therapies in lung adenocarcinoma - Manjiao Liu; Meijia Yang; Bei Zhang; Sijian Xia; Jie Zhao; Linlin Yan; Yong Ren; Hao Guo; Jie Zhao (Journal of Molecular Medicine, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Effect-directed analysis of androgenic compounds from sewage sludges in China - Tongtong Xiang; Chunzhen Shi; Yunhe Guo; Jie Zhang; Weicui Min; Jiazheng Sun; Jifu Liu; Xiliang Yan; Yanna Liu; Linlin Yao; Yuxiang Mao; Xiaoxi Yang; et al. (Water Research, 2024)

Evidence and causes of recent decreases in nitrogen deposition in temperate forests in Northeast China - Yingying Wang; Feifei Zhu; Jin Li; Geshere Abdisa Gurmesa; Shaonan Huang; Xiaoming Fang; Dongwei Liu; Abubakari Said Mgelwa; Wenchao Wang; Kai Huang; Yihang Duan; Linlin Song; et al. (Science of The Total Environment, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

Copper-doped ZIF-67/wood aerogel for effective peroxymonosulfate activation - Linlin Zhao; Wanning Xiong; Ziheng Wang; Jie Ouyang; Mengyao Li; Gonggang Liu; Yongfeng Luo (Journal of Environmental Chemical Engineering, 2024)

Cellulose-based magnetic nanomaterials immobilized esterases as a reusable and effective detoxification agent for patulin in apple juice - Xiaoshuang Liu; Linlin Gao; Shiqi Li; Leran Wang; Rui Cai; Tianli Yue; Yahong Yuan; Xubo Zhao; Zhouli Wang (Food Control, 2024)

Polycyclic aromatic hydrocarbons exposure and arterial stiffness-related plasma miRNAs: A panel study - Ziqian Zhang; Conghua Bai; Lei Zhao; Linlin Liu; Wenting Guo; Miao Liu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Toxicology and Pharmacology, 2024)

Activatable theranostic nanoprobes for Fluorescence/MR imaging and microenvironment remodeling of early cartilage degeneration - Xiuli Zhang; Manman Xie; Linlin Li; Wenlou Liu; Peng Xu; Zuohui Zhang; Yue Dai; Dongxu Wang; Li Lu; Kai Xu; Jingjing Li (Chemical Engineering Journal, 2024)

An end-capping strategy for shape memory phthalonitrile resins via annealing enables conductivity and wave-absorption - Rongxiang Hu; Fenghua Zhang; Lan Luo; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2024)

Rapid Diagnosis of Pneumocystis jirovecii Pneumonia and Respiratory Tract Colonization by Next-Generation Sequencing - Fanfan Xing; Chaowen Deng; Zhendong Luo; Shan Zou; Min Liu; Haiyan Ye; Linlin Sun; Chi-Ching Tsang; Simon K. F. Lo; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2024)
Objectives To describe the epidemiology of Pneumocystis jirovecii pneumonia and colonization diagnosed by next-generation sequencing (NGS) and explore the usefulness of the number of P. jirovecii sequence reads for the diagnosis of P. jirovecii pneumonia. Methods We examined the NGS results for P. jirovecii in respiratory samples collected from patients and analysed their clinical, radiological and microbiological characteristics. Results Among 285 respiratory samples collected over a 12-month period (January to December 2022), P. jirovecii sequences were detected in 56 samples from 53 patients. Fifty (94.3%) of the 53 patients were HIV-negative. Following our case definitions, 37 (69.8%) and 16 (30.2%) of the 53 patients had P. jirovecii infection and colonization respectively. P. jirovecii infection was associated with presence of underlying disease with immunosuppression (94.6% vs 18.8%, P < 0.05), positive serum 1,3-β-D-glucan (41.2% vs 0%, P < 0.01) and higher number of P. jirovecii sequence reads ( P < 0.005). In contrast, P. jirovecii colonization was associated with the male sex (93.8% vs 54.1%, P < 0.01), another definitive infectious disease diagnosis of the respiratory tract (43.8% vs 2.7%, P < 0.001) and higher survival (100% vs 67.6%, P < 0.01). Although P. jirovecii pneumonia was associated with higher number of P. jirovecii reads in respiratory samples, only a sensitivity of 82.14% and a specificity of 68.75% could be achieved. Conclusion Detection of P. jirovecii sequences in respiratory samples has to be interpreted discreetly. A combination of clinical, radiological and laboratory findings is still the most crucial in determining whether a particular case is genuine P. jirovecii pneumonia.

Airborne ARGs/MGEs from two sewage types during the COVID-21: Population, microbe interactions, cytotoxicity, formation mechanism, and dispersion - Yanjie Wang; Song Zhang; Lin Li; Qiao Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Jian Wu; Linlin Hua (Water Research, 2024)

Spatiotemporal distribution, interactions and toxic effect of microorganisms and ARGs/MGEs from the bioreaction tank in hospital sewage treatment facility - Yanjie Wang; Song Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Lin Li; Linlin Hua (Science of The Total Environment, 2024)

Prenatal exposure to poly/perfluoroalkyl substances and risk for congenital heart disease in offspring - Sainan Li; Chengrong Wang; Chen Yang; Yongyan Chen; Qianhui Cheng; Jufen Liu; Yali Zhang; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2024)

Review on post-combustion CO2 capture by amine blended solvents and aqueous ammonia - Jiaxing Du; Wu Yang; Linlin Xu; Lei Bei; Siyuan Lei; Wei Li; Haitao Liu; Ben Wang; Lushi Sun (Chemical Engineering Journal, 2024)

Bioaerosols in deodorization covers of wastewater treatment plants: Emission characteristics and health risks - Shan Zhao; Yang Liu; Jiang Chang; Jiawei Wang; Hao Peng; Baocong Cui; Jin Bai; Yanjie Wang; Linlin Hua (Chemosphere, 2024)

Dual-objective control of braced steel frame using asynchronized parallel two-stage yielding BRB - Cantian Yang; Linlin Xie; Qiang Liu; Aiqun Li; Qianmin Liu; Xinyu Wang (Soil Dynamics and Earthquake Engineering, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

A review of indoor nitrous acid (HONO) pollution: Measurement techniques, pollution characteristics, sources, and sinks - Chang Liu; Linlin Liang; Wanyun Xu; Qingxin Ma (Science of The Total Environment, 2024)

Microdrop-confined synthesis and regulation of porous hollow Ir-based catalysts for the mass transfer-enhanced electrolysis of pure water - Li Liu; Ting Huang; Xiaoliang Yang; Shoujie Liu; Shunsheng Wang; Linlin Xiang; Gongming Wang; Long Kuai (Science Bulletin, 2024)

High spatial and temporal resolution multi-source anthropogenic heat estimation for China - Jiangkang Qian; Linlin Zhang; Uwe Schlink; Qingyan Meng; Xue Liu; Tamás Janscó (Resources, Conservation and Recycling, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Experimental investigation of propeller blade back cavitation induced pressure pulses by synchronous observation - Rui Wu; Heng Liu; Weiqi Chen; Sheng Ji; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2024)

Quantifying the environmental synergistic effect of cooling-air purification-carbon sequestration from urban forest in China - Rundong Feng; Shenghe Liu; Fuyuan Wang; Kaiyong Wang; Ping Gao; Linlin Xu (Journal of Cleaner Production, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

Effects of glutenin/gliadin ratio and calcium ion on the structure and gelatinity of wheat gluten protein under heat induction - Min Qu; Peixiu Jiang; Ying Zhu; Xiuqing Zhu; Linlin Liu; Yuyang Huang (Food Bioscience, 2024)

Evolution behavior of volatile components of shiitake mushrooms during infrared-assisted spouted bed drying - Yiming Xu; Wenchao Liu; Linlin Li; Weiwei Cao; Guangyue Ren; Houdong Shi; Yike Zhao; Junliang Chen; Xu Duan (Food Control, 2024)

Ginsenoside Rk1 induces autophagy-dependent apoptosis in hepatocellular carcinoma by AMPK/mTOR signaling pathway - Huanyan Wu; Linlin Qu; Xue Bai; Chenhui Zhu; Yuan Liu; Zhiguang Duan; Hongyan Liu; Rongzhan Fu; Daidi Fan (Food and Chemical Toxicology, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Changes of microbial residues over century-long soil development after tidal flat reclamation in eastern China - Dezhi Yan; Weiyue Sun; Linlin Ye; Bo Liu (CATENA, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Clinical Application of Polygenic Risk Score in IgA Nephropathy - Linlin Xu; Ting Gan; Pei Chen; Yang Liu; Shu Qu; Sufang Shi; Lijun Liu; Xujie Zhou; Jicheng Lv; Hong Zhang (Phenomics, 2024)

In Utero Exposure to Lead is Associated with Neural Tube Defects via Disturbing the Expression of Endocannabinoid Retrograde Signaling-Related Genes - Tian Tian; Huijun Dong; Shengju Yin; Mengyuan Liu; Yongyan Chen; Kuanhui Xiang; Linlin Wang; Jie Qiao; Aiguo Ren (Exposure and Health, 2024)

Estimating the methane flux of the Dajiuhu subalpine peatland using machine learning algorithms and the maximal information coefficient technique - Xue Li; Jiwen Ge; Ziwei Liu; Shiyu Yang; Linlin Wang; Ye Liu (Science of The Total Environment, 2024)

Interactive effects of dinotefuran and Nosema ceranae on the survival status and gut microbial community of honey bees - Linlin Liu; Min Shi; Yanyan Wu; Xianbing Xie; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2024)

Simplified mechanical calculation model for an entire jack-up platform system - Linlin He; Yuanshi Xie; Yizhong Du; Yang Liu; Mingwei Liu (Ocean Engineering, 2024)

Tissue-specific distribution and bioaccumulation of perfluoroalkyl acids, isomers, alternatives, and precursors in citrus trees of contaminated fields: Implication for risk assessment - Zhaoyang Liu; Shun Liu; Feng Xiao; Andrew J. Sweetman; Qianqian Cui; Hao Guo; Jiayi Xu; Ziyao Luo; Mingxia Wang; Linlin Zhong; Jay Gan; Wenfeng Tan (Journal of Hazardous Materials, 2024)

Quantitative distribution and quantized ecological threat of microplastics in farmland: Shanghai as an example - Zhengwen Li; Zhaofeng Song; Linlin Qiu; Yan Cao; Hairong Gu; Zhenqi Wang; Xiang Liu; Xiaoyong Qian (Journal of Hazardous Materials, 2024)

Influence of polysaccharide-based co-encapsulants on efficiency, stability, and release of vitamins B12 and D3 in multilayered microcapsules - Linlin He; Shihong Hu; Gang Zhang; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhengping Wang; Prakash Sangeeta; Zhuang Ding (Journal of Food Engineering, 2024)

Release characteristics and risk assessment of volatile sulfur compounds in a municipal wastewater treatment plant with odor collection device - Linlin Ma; Ruhan Zhao; Jiaxin Li; Qing Yang; Yong Liu (Journal of Environmental Management, 2024)

Preparation and characterization of zein-tannic acid nanoparticles/chitosan composite films and application in the preservation of sugar oranges - Shuangjian Li; Xiaoli Liu; Xiaoqian Zhang; Linlin Fan; Fan Wang; Jianzhong Zhou; Hongzhi Zhang (Food Chemistry, 2024)

UV-B application during the aeration process improves the aroma characteristics of oolong tea - Xiaohui Wang; Jingjie Cao; Xin Cheng; Xuyang Liu; Wenfeng Zhu; Yan Li; Xiaochun Wan; Shengkeng Chen; Linlin Liu (Food Chemistry, 2024)

A novel baking additive: Preparation, characterization, and application of chitosan hydrochloride/carboxymethyl starch sodium nano-gel for wheat bread - Xinlai Dou; Yanling Hao; Ying Sun; Pin Yang; Linlin Liu; Yinyuan He; Yanguo Shi; Chunhua Yang; Fenglian Chen (Food Hydrocolloids, 2024)

Piezoelectric effect-assisted Z-scheme heterojunction ZnIn2S4/BaTiO3 for improved photocatalytic reduction of CO2 to CO - Shanyue Lu; Shengwei Zhang; Linlin Li; Cong Liu; Zhou Li; Dan Luo (Chemical Engineering Journal, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

The mediation effect of asprosin on the association between ambient air pollution and diabetes mellitus in the elderly population in Taiyuan, China - Lulu Song; Yuhui Gao; Jiayu Tian; Nannan Liu; Halimaimaiti Nasier; Caihong Wang; Huiqiu Zhen; Linlin Guan; Zeyu Niu; Dongxing Shi; Hongmei Zhang; Lifang Zhao; et al. (Environmental Science and Pollution Research, 2024)

Analysis of Flow Instability and Mechanical Energy Loss of Fluid Field in Fluid Momentum Wheel - Kedong Zhang; Wenhua Wang; Yihua Liu; Linlin Wang; Yazhen Du; Hongxia Li; Yi Huang (Journal of Marine Science and Engineering, 2024)
A new type of anti-rolling device denoted as a fluid momentum wheel (FMW) is proposed to address the limitations of traditional gyrostabilizers in reducing the roll responses of floating platforms in waves. The proposed device is based on the same gyroscope theorem, which differs from a rigid gyrostabilizer in that the internal fluid generates secondary flow in the cross-section under the combined effects of inertial centrifugal force and a radial pressure gradient, and the streamwise velocity exhibits a non-uniform distribution. These instability phenomena may cause mechanical energy loss in the flow field, which is critical for selecting the driving device and the anti-roll control performance of offshore platforms. In the study, different turbulence models are compared with the results of a Direct Numerical Simulation (DNS) and experiments to ensure the accuracy of the numerical method, and the spatiotemporal distribution characteristics of the flow field in FMW are analyzed. Therein, the SST k-ω model accurately verifies the flow instability phenomenon of the FMW observed in the Particle Image Velocimetry (PIV) experiment. Next, this paper proposes corresponding evaluation parameters to assess the impact of typical parameters on the flow field instability. The results show that the flow instability increases with an increase in the typical parameters of FMWs (such as the pipe diameter, curvature radius, and velocity). Furthermore, the paper discusses the relationship between dimensionless mechanical factors (Reynolds number, curvature ratio) and the spatiotemporal instability of the flow field, revealing the essential effects of the curvature ratio and Reynolds number on the loss coefficient.

The miR-34b/MEK/ERK pathway is regulated by NR5A1 and promotes differentiation in primary bovine Sertoli cells - Qibing Tao; Linlin Zhang; Yun Zhang; Mingming Liu; Jie Wang; Qian Zhang; Jiancheng Wu; Aihua Wang; Yaping Jin; Keqiong Tang (Theriogenology, 2024)

Electrocatalytic degradation of nitrogenous heterocycles on confined particle electrodes derived from ZIF-67 - Yu Liu; Linlin Qin; Yiming Qin; Tong Yang; Haoran Lu; Yulong Liu; Qiqi Zhang; Wenyan Liang (Journal of Hazardous Materials, 2024)

Cu-hierarchical porous carbon anodes derived from metal-organic frameworks for long-lasting and high-energy lithium storage - Bing Zhu; Manshu Zhang; Yangai Liu; Yicen Liu; Xi Zhang; Yahui Song; Linlin Wang; Ruiyu Mi (Chemical Engineering Journal, 2024)

Selective fluoride removal from groundwater using CNT-CeO2 electrodes in capacitive deionization (CDI) - Xun Liu; Danyal Rehman; Yufei Shu; Bei Liu; Li Wang; Li Li; Mengxia Wang; Kunkun Wang; Qi Han; Linlin Zang; John H. Lienhard; Zhongying Wang (Chemical Engineering Journal, 2024)

Structure-defined viologen-polyoxometalate modified separator dominating endurable Li-S batteries by a synergistic adsorption-electrocatalysis mechanism - Yuxi Zhang; Yundong Cao; Linlin Fan; Guilin Shi; Tianyu Zheng; Hong Liu; Jian Song; Guanggang Gao (Chemical Engineering Journal, 2024)

Colorimetric microneedle sensor using deep learning algorithm for meat freshness monitoring - Jie Wang; Linlin Xia; Han Liu; Chong Zhao; Siyu Ming; Jingyi Wu (Chemical Engineering Journal, 2024)

Alisol A Exerts Neuroprotective Effects Against HFD-Induced Pathological Brain Aging via the SIRT3-NF-κB/MAPK Pathway - Taotao Lu; Linlin Ding; Xiaoqing Zheng; Yongxu Li; Wei Wei; Weilin Liu; Jing Tao; Xiehua Xue (Molecular Neurobiology, 2024)
Chronic consumption of a high-fat diet (HFD) has profound effects on brain aging, which is mainly characterized by cognitive decline, inflammatory responses, and neurovascular damage. Alisol A (AA) is a triterpenoid with therapeutic potential for metabolic diseases, but whether it has a neuroprotective effect against brain aging caused by a HFD has not been investigated. Six-month-old male C57BL6/J mice were exposed to a HFD with or without AA treatment for 12 weeks. Behavioral tasks were used to assess the cognitive abilities of the mice. Neuroinflammation and changes in neurovascular structure in the brains were examined. We further assessed the mechanism by which AA exerts neuroprotective effects against HFD-induced pathological brain aging in vitro and in vivo. Behavioral tests showed that cognitive function was improved in AA-treated animals. AA treatment reduced microglia activation and inflammatory cytokine release induced by a HFD. Furthermore, AA treatment increased the number of hippocampal neurons, the density of dendritic spines, and the expression of tight junction proteins. We also demonstrated that AA attenuated microglial activation by targeting the SIRT3-NF-κB/MAPK pathway and ameliorated microglial activation-induced tight junction degeneration in endothelial cells and apoptosis in hippocampal neurons. The results of this study show that AA may be a promising agent for the treatment of HFD-induced brain aging.

Vertical distribution of intraseasonal variation signals in the Kuroshio Current source area during 2018–2020 - Haobo Gong; Fujun Wang; Feng Liu; Linlin Zhang; Dunxin Hu (Frontiers in Marine Science, 2024)
In the Kuroshio Current (KC) source area, intraseasonal variation (ISV) plays a significant role in dynamic oceanic processes. This study used data collected from three moorings (122.7°E, 123°E, 123.3°E) along 18°N from January 2018 to May 2020 to investigate the ISVs of meridional velocities. Notably, our findings reveal that the ISV above 200 m has a period of approximately 56 days and its intensity exhibits a gradual increase toward the west. For the 500–800 m depth interval, the ISV period is 73 days at 122.7°E/18°N and 60 days at 123.3°E/18°N. This discrepancy indicates that the ISVs have different vertical structures and frequencies at 122.7°E and 123.3°E along 18°N. In particular, at 122.7°E/18°N, the distinctiveness of two different periods of ISVs in surface and subsurface layers was more pronounced in 2018 than in 2019. The analyses of eddy kinetic energy distribution and eddy tracking indicate a connection between ISV in stratification and locally generated mesoscale eddies in the KC source area. Specifically, the stronger eddy activity in 2018, in contrast with that in 2019, correlates with a more pronounced ISV. Energy analysis demonstrates a distinct positivity in the baroclinic conversion rate (BC) in the surface layer (upper 200 m) of the KC source region, surpassing the absolute value of the barotropic conversion rate (BT). This finding indicates a notable shift of energy from eddy available potential energy to eddy kinetic energy, strengthening the high-frequency ISV signals in this area. In the subsurface layer, a strong negative BT is observed west of 122.8°E, with its absolute value exceeding the BC. This finding indicates that the energy is converted from eddy kinetic energy into mean kinetic energy, resulting in the appearance of the Luzon Undercurrent (LUC) at mooring station 122.7°E/18°N, characterized by a low frequency of ISV. Contrastingly, a positive BT plays a dominant role at 123.3°E/18°N, leading to the disappearance of the LUC amid an apparent presence of high-frequency ISV.

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

Seismic behavior of embedded rubberized concrete-filled corrugated steel tube column-to-foundation connections: Experimental, numerical modelling, and design - Mingyang Feng; Baodong Liu; Linlin Zhang; Yaoyao Wang; Haibo Sun (Soil Dynamics and Earthquake Engineering, 2024)

GhFB15 is an F-box protein that modulates the response to salinity by regulating flavonoid biosynthesis - Zhao Geng; Haikuan Dou; Jianguang Liu; Guiyuan Zhao; Zetong An; Linlin Liu; Ning Zhao; Hanshuang Zhang; Yongqiang Wang (Plant Science, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

Patterns and drivers of atmospheric inorganic nitrogen deposition in Northeast Asia - Abubakari Said Mgelwa; Feifei Zhu; Dan Huang; Linlin Song; Yingying Wang; Geshere Abdisa Gurmesa; Ang Wang; Miao Liu; Shaonan Huang; Qingyan Qiu; Hiroyuki Sase; Weixing Zhu; et al. (Journal of Environmental Management, 2024)

Fabrication and mechanism of La/Al bimetallic organic frameworks for phosphate removal - Zheng Zhu; Linlin Qin; Yulong Liu; Qiqi Zhang; Peng Cheng; Wenyan Liang (Chemical Engineering Journal, 2024)

Angiotensin II type 2 receptor agonist attenuates LPS-induced acute lung injury through modulating THP-1-derived macrophage reprogramming - Liangzhi Chen; Ping Gong; Yue Su; Linlin Meng; Muyun Wang; Wei Gao; Qinghua Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Assessing the impact of marketization on energy poverty - Xinjie Shi; Pei Zeng; Liu Cui; Xuwen Gao; Tongwei Qiu; Qiang Jiang; Linlin Fu (Environment, Development and Sustainability, 2023)

Applying an ensemble of small models in predicting habitat suitability of invasive M. sallei along the southern coast of China - Hao Dong; Jie Liu; Linlin Zhao; Changdong Liu (Marine Pollution Bulletin, 2023)

Full-scale experimental study on seismic performance of repaired precast shear walls - Xinyu Wang; Linlin Xie; Qianmin Liu (Soil Dynamics and Earthquake Engineering, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Multidimensional cross-linked network strategies for Rapidly, Reconfigurable, refoldable shape memory polymer - Lan Luo; Fenghua Zhang; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

circ_SPEF2 Regulates the Balance of Treg Cells by Regulating miR-16-5p/BACH2 in Lymphoma and Participates in the Immune Response - Jie Zhou; Min Xu; ZhaoZhao Chen; LinLin Huang; ZhuoLin Wu; ZhongPei Huang; Lin Liu (Tissue Engineering and Regenerative Medicine, 2023)

Phase Transition in Geomaterials Under Unsaturated Conditions - Jiuhui Cheng; Xuanzhe Xia; Zhiqiang Liu; Linlin Wang (Rock Mechanics and Rock Engineering, 2023)

Integrated analyses delineate distinctive immunological pathways and diagnostic signatures for Behcet’s disease by leveraging gene microarray data - Haoting Zhan; Linlin Cheng; Haolong Li; Yongmei Liu; Yuan Huang; Xiaomeng Li; Songxin Yan; Yongzhe Li (Immunologic Research, 2023)

Hippocampal subfield volumes in mild cognitive impairment and alzheimer’s disease: a systematic review and meta-analysis - Jinhuan Zhang; Linlin Xie; Changjiang Cheng; Yongfeng Liu; Xiaodong Zhang; Haoyu Wang; Jingting Hu; Haibo Yu; Jinping Xu (Brain Imaging and Behavior, 2023)

Rhizosphere effects on the microbial community: Specificity and conservatism across geographically disjunct Panax species - Guozhuang Zhang; Liping Shi; Congsheng Liu; Zhixin Huang; Yuqing Zheng; Linlin Dong (Applied Soil Ecology, 2023)

Does environmental policy stringency influence CO2 emissions in the Asia Pacific region? A nonlinear perspective - Linlin Liu; Liwei Pang; Hong Wu; Muhammad Hafeez; Raufhon Salahodjaev (Air Quality, Atmosphere & Health, 2023)

An Extreme Gale Event in East China under the Arctic Potential Vorticity Anomaly through the Northeast China Cold Vortex - Wei Tao; Linlin Zheng; Ying Hao; Gaoping Liu (Advances in Atmospheric Sciences, 2023)

Insight into the mechanisms of neuroendocrine toxicity induced by 6:2FTCA via thyroid hormone disruption - Linlin Wu; Jie Gu; Xinjie Duan; Feng Ge; Heyong Ye; Lingcan Kong; Wenwei Liu; Rong Gao; Jiandong Jiao; Huanhuan Chen; Guixiang Ji (Chemosphere, 2023)

PM2.5-bound metals and blood metals are associated with pulmonary function and Th17/Treg imbalance: A panel study of asthmatic adults - Nannan Liu; Dan Wang; Jiayu Tian; Xin Wang; Hao Shi; Caihong Wang; Yi Jiang; Min Pang; Xiaozhou Fan; Jing Zhao; Liangpo Liu; Hongyan Wu; et al. (Chemosphere, 2023)

Associations among bisphenol A, its analogs, and chlorinated derivatives in placenta and risk for neural tube defects: A case-control study - Haiyan Zhu; Qianhui Cheng; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2023)

Biomineralization of uranium by Desulfovibrio desulfuricans A3-21ZLL under various hydrochemical conditions - Bei Zhao; Xin Chen; Hongliang Chen; Linlin Zhang; Jiang Li; Yadan Guo; Haiyan Liu; Zhongkui Zhou; Pingchao Ke; Zhanxue Sun (Environmental Research, 2023)

A review of adsorption materials and their application of 3D printing technology in the separation process - Jiangtao Yu; Jie Zhu; Linlin Chen; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Chemical Engineering Journal, 2023)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

A lipidomic approach to bisphenol F-induced non-alcoholic fatty liver disease-like changes: altered lipid components in a murine model - Xinjing Wang; Linlin Wu; Jingxian Tao; Heyong Ye; Jun Wang; Rong Gao; Wenwei Liu (Environmental Science and Pollution Research, 2023)

Experimental and theoretic mechanism of successive adsorption of oppositely charged Cu(II) and Cr(VI) onto amine-rich cellulose adsorbent - Linlin Hao; Dongmei Jia; Mengzhu Liu (Environmental Science and Pollution Research, 2023)

A quantitative analysis of the impact of reclamation on the stability of coastal wetlands - Yanhui Chen; Linlin Cui; Guosheng Li; Jiping Liu; Lijuan Li; Dandan Zhao (Ocean & Coastal Management, 2023)

Solar forcing and ENSO regulated rates of change of ecosystems in Northeast China since the last deglaciation - Guizai Gao; Honghao Niu; Lina Song; Jiangyong Wang; Meng Meng; Zhuo Yang; Linlin Liu; Yuanxiang Wei; Niankang Chen; Jihuai Yu; Dongmei Jie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Reaction pathways control of long-chain alkanes hydroisomerization and hydrocracking via tailoring the metal-acid sites intimacy - Wenli Zhao; Linlin Liu; Xiaopo Niu; Xinyue Yang; Jiuyi Sun; Qingfa Wang (Fuel, 2023)

Effect of Na+ and Ca2+ on the texture, structure and microstructure of composite protein gel of mung bean protein and wheat gluten - Ruqi Guo; Linlin Liu; Yuyang Huang; Mingshou Lv; Ying Zhu; Zihan Wang; Xiuqing Zhu; Bingyu Sun (Food Research International, 2023)

Engineering effect of oleogels with different structuring mechanisms on the crystallization behavior of cocoa butter - Linlin Li; Guoqin Liu (Food Chemistry, 2023)

An ultra-stable high entropy metal nitride for aerobic oxidative desulfurization and source recovery of aromatic sulfides from fuel oils - Peiwen Wu; Chang Deng; Penghui Liu; Feng Liu; Linlin Chen; Bangzhu Wang; Wenshuai Zhu; Chunming Xu (Chemical Engineering Journal, 2023)

Novel electron donor boosting the electron supply capacity of hierarchical structure carbon nitride for efficient photocatalytic hydrogen peroxide production - Linlin Sun; Xiaoshuo Liu; Huiling Ji; Xunlei Ding; Nan Jiang; Jigang Wang (Chemical Engineering Journal, 2023)

Gas-pressurized torrefaction of lignocellulosic solid wastes: Low-temperature deoxygenation and chemical structure evolution mechanisms - Liu Shi; Zhenzhong Hu; Xian Li; Shuo Li; Linlin Yi; Xiaohua Wang; Hongyun Hu; Guangqian Luo; Hong Yao (Bioresource Technology, 2023)

Improved biomass burning pollution in Beijing from 2011 to 2018 - Linlin Liang; Zhenyu Du; Guenter Engling; Xuyan Liu; Wanyun Xu; Chang Liu; Yuan Cheng; Dongsheng Ji; Gen Zhang; Junying Sun (Atmospheric Environment, 2023)

Exploring the therapeutic mechanism of Banxia Xiexin Decoction in mild cognitive impairment and diabetes mellitus: a network pharmacology approach - Cong Li; Wei Yang; Yubo Meng; Lina Feng; Linlin Sun; Zhenghong Li; Xingfang Liu; Mingquan Li (Metabolic Brain Disease, 2023)

Optimal design of carbon utilization business model and dynamic investment decision-making in complex conditions - Wei Han; Linlin Liu (Environment, Development and Sustainability, 2023)

A novel framework for combining polarimetric Sentinel-1 InSAR time series in subsidence monitoring - A case study of Sydney - Alex Hay-Man Ng; Ziyue Liu; Zheyuan Du; Hengwei Huang; Hua Wang; Linlin Ge (Remote Sensing of Environment, 2023)

Quadristerols A−G: Seven undescribed ergosterols from Aspergillus quadrilineata - Mengsha Wei; Xiaoxin Li; Hong Liao; Linlin Liu; Qin Li; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2023)

Occurrence of fungi and mycotoxins in herbal medicines and rapid detection of toxin-producing fungi - Guangfei Wei; Xiaotong Guo; Yichuan Liang; Congsheng Liu; Guozhuang Zhang; Conglian Liang; Zhixin Huang; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Pollution, 2023)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Geranylgeranylacetone, an inducer of heat shock protein 70, attenuates pulmonary fibrosis via inhibiting NF-κB/NOX4/ROS signalling pathway in vitro and in vivo - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Chemico-Biological Interactions, 2023)

GGA (geranylgeranylacetone) ameliorates bleomycin-induced lung inflammation and pulmonary fibrosis by inhibiting apoptosis and oxidative stress - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Molecular Biology Reports, 2023)

Exploration on the reasons for low efficiency of arable land protection policy in China: an evolutionary game theoretic model - Linlin Wang; Zhuo Li; Chengcheng Yuan; Liming Liu (Environment, Development and Sustainability, 2023)

Paleoproterozoic skarn mineralization events and geodynamic background in the Jiao-Liao-Ji Belt: Geological, geochemical and chronological evidence from the Daqinggou Fe–Cu polymetallic deposit in Ji'an, NE China - YanPeng Liu; JingGui Sun; LinLin Wang; ZhiKai Xu; ChengLin Bai; Xiang Chang; TingTing Zhang (Precambrian Research, 2023)

Urinary phthalate metabolites and heart rate variability: A panel study - Ziqian Zhang; Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Jie Yu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Pollution, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

Effect of Environmental Factors on Performance of Bioreactor with Immobilized Petroleum-Degrading Bacteria Beads - Yixuan Liu; Yue Dun; Jianliang Xue; Yu Gao; Dongle Cheng; Yanlu Qiao; Linlin Zhang (Water, Air, & Soil Pollution, 2023)

On the effects of rheological behavior on landslide motion and tsunami hazard for the Baiyun Slide in the South China Sea - Zhiyuan Ren; Hua Liu; Linlin Li; Yuchen Wang; Qiliang Sun (Landslides, 2023)

Prognostic value of the WT-1 gene combined with recurrent cytogenetic genes in acute myeloid leukemia - Qing Zhang; Linlin Liu; Haotian Yan; Xiyang Ren; Mei Zhou; Shudao Xiong; Huiping Wang; Qianshan Tao; Zhimin Zhai (Immunogenetics, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

High-pressure synthesis of fully sp2-hybridized polymeric nitrogen layer in potassium supernitride - Minghong Sui; Shuang Liu; Peng Wang; Nianlong Zou; Qing Dong; Miao Zhou; Shifeng Niu; Lei Yue; Zitong Zhao; Linlin Guo; Bo Liu; Ran Liu; et al. (Science Bulletin, 2023)

Corrigendum to “Self-assembly of Fe3O4 with natural tannin as composites for microalgal harvesting” [Fuel 321 (2022) 124038] - Xiaoyu Wang; Chuang Liu; Linlin Qin; Wenyan Liang (Fuel, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

Genetic diversity and population structure of the sea star Asterias amurensis in the northern coast of China - Quanchao Wang; Ying Liu; Zirui Peng; Linlin Chen; Baoquan Li (Journal of Oceanology and Limnology, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Strategies for mapping protein hydrolysate profiles and pharmacokinetics based on non-targeted proteomics combining skyline-aided quantitative techniques - Shuying Mao; Wei Jin; Sisi Fu; Keanqi Liu; Feng Xu; Linlin Wu; Yexin Xu; Huizhu Yang; Huafang Liu; Guangji Wang; Yan Liang (Analytica Chimica Acta, 2023)

Seasonal distribution of the early life stages of the small yellow croaker ( Larimichthys polyactis ) and its dynamic controls adjacent to the Changjiang River Estuary - Min Xu; Yihe Wang; Zunlei Liu; Yong Liu; Yi Zhang; Linlin Yang; Fei Wang; Hui Wu; Jiahua Cheng (Fisheries Oceanography, 2023)
The distribution of the early life stages of Larimichthys polyactis indicates the availability of suitable spawning and nursing grounds and enables a better understanding of the distribution of its geographic subpopulations and isolation. Large‐scale quantitative ichthyoplankton surveys of L. polyactis were performed from March to July 2018, and a numerical hydrodynamic model was applied to explore the spatiotemporal distribution and habitats of L. polyactis early life stages adjacent to the Changjiang River Estuary. Two distinct early life stage distribution patterns were found. One occurred during March and April in the deep waters seaward of the Changjiang River bottom plume front, to the east and southeast of the Changjiang River Estuary. The other occurred in May and June throughout the entire water column in coastal waters to the east and north of the Changjiang River Estuary. Rising seasonal temperatures, and the local dynamic processes such as the Changjiang River plume, determined the transitions between the two distribution patterns. A potential fish larval migration route from the southern deep shelf waters to the northern coastal waters within the motor‐trawl prohibition line was suggested. This study contributes to our understanding of the mixture of habitats used by the two L. polyactis subpopulations in the southern Yellow Sea and the East China Sea.

Occurrence of legacy and alternative per- and polyfluoroalkyl substances in serum from high exposure population and their disrupting effects on serum lipids and thyroid function - Jiaying Liu; Linlin Song; Jing Zhan; Yunxin Zhong; Zhixiong Shi (Science of The Total Environment, 2023)

In vitro gastrointestinal digestion of whole grain noodles supplemented with soluble dietary fiber and their effects on children fecal microbiota - Linlin Gao; Lin Zhang; Huan Liu; Jielun Hu (Food Bioscience, 2023)

Elevation-dependent tree growth response to recent warming and drought on eastern Tibetan Plateau - Dingcai Yin; Xiaohua Gou; Haijiang Yang; Kai Wang; Jie Liu; Yiran Zhang; Linlin Gao (Climatic Change, 2023)

Defensive Specialized Metabolites from the Latex of Euphorbia jolkinii - Shihong Luo; Chunshuai Huang; Juan Hua; Shuxi Jing; Linlin Teng; Ting Tang; Yan Liu; Shenghong Li (Journal of Chemical Ecology, 2023)

Influence Mechanism of New-type Urbanization on Urban Land Use Efficiency in the Yangtze River Delta, China - Qingke Yang; Linlin Ding; Lei Wang; Chao Liu; Yeting Fan; Ying Li; Yazhu Wang (Chinese Geographical Science, 2023)

Role of local climate zones and urban ventilation in canopy urban heat island–heatwave interaction in Nanjing megacity, China - Weishou Tian; Yuanjian Yang; Linlin Wang; Lian Zong; Yanhao Zhang; Duanyang Liu (Urban Climate, 2023)

Buckling failure mechanism and critical buckling load prediction method of super-long piles in soft-clay ground in deep water - Linlin He; Zhisong Li; Yuanshi Xie; Yang Liu; Mingwei Liu (Ocean Engineering, 2023)

Biosynthesis of pectic oligosaccharide-based amphiphiles as novel stabilizers of nanoemulsions by coupling enzymatic depolymerization with alkyl/alkenyl succinylation - Linlin Li; Ziqian Li; Thomas Balle; Guoqin Liu; Zheng Guo (Food Hydrocolloids, 2023)

Self-powered energy harvesting and implantable storage system based on hydrogel-enabled all-solid-state supercapacitor and triboelectric nanogenerator - Zhuo Wang; Shuncheng Yao; Shaobo Wang; Zhirong Liu; Xingyi Wan; Quanhong Hu; Yunchao Zhao; Cheng Xiong; Linlin Li (Chemical Engineering Journal, 2023)

Allosteric synthetic antibody (Allo-SyAb) for improved cancer immunotherapy - Jiajing Chen; Mengchen Xu; Yongxin Zhang; Linlin Xu; Shuyue Zhao; Yingli An; Rujiang Ma; Yang Liu; Feihe Ma; Linqi Shi (Chemical Engineering Journal, 2023)

Unevenly spatiotemporal distribution of urban excess warming in coastal Shanghai megacity, China: Roles of geophysical environment, ventilation and sea breezes - Yuanjian Yang; Min Guo; Linlin Wang; Lian Zong; Duanyang Liu; Wenjie Zhang; Mengya Wang; Bingcheng Wan; Yide Guo (Building and Environment, 2023)

Singlet oxygen generation in light-assisted peroxymonosulfate activation by carbon nitride: Role of elevated crystallinity - Beizhao Chen; Xun Liu; Bei Liu; Qi Han; Li Li; Li Wang; Yufei Shu; Linlin Zang; Wenlei Zhu; Zhongying Wang (Chemosphere, 2023)

Global analysis of gene expression profiles and gout symptoms in goslings infected with goose astrovirus - Chenggang Liu; Linlin Li; Jiawen Dong; Junqin Zhang; Yunzhen Huang; Qi Zhai; Yong Xiang; Jin Jin; Xianshe Huang; Gang Wang; Minhua Sun; Ming Liao (Veterinary Microbiology, 2023)

Development of SSR markers on the basis of the Panax notoginseng transcriptome for agronomic and biochemical trait association analyses - Linlin Su; Yingpeng Zhang; Ye Yang; Yuan Qu; Xiuming Cui; Feng Ge; Diqiu Liu (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Comparison and quantification of estrogen receptor-mediated responsiveness to endocrine disruptors in bivalves by using complementary model and a novel yeast assay approach - Liru Liu; Jingjing Miao; Peipei Liu; Anran Zhao; Linlin Yao; Luqing Pan (Environmental Pollution, 2023)

UV-B regulates seasonal greening of albino leaves by modulating CsHY5-inhibiting chlorophyll biosynthesis in Camellia sinensis cv. Huangkui - Xuyang Liu; Xin Cheng; Jingjie Cao; Wenfeng Zhu; Ying Sun; Ning Lin; Xiaochun Wan; Linlin Liu (Plant Science, 2023)

Recent advances of plasmonic elemental Bi based photocatalysts in environmental remediation and energy conversion - Cailiang Yue; Linlin Zhu; Yixing Qiu; Zhiling Du; Jinli Qiu; Fuqiang Liu; Fenghe Wang (Journal of Cleaner Production, 2023)

Rhizobacteria helps to explain the enhanced efficiency of phytoextraction strengthened by Streptomyces pactum - Linlin Wang; Nina Wang; Di Guo; Zhengzheng Shang; Yiying Zhang; Song Liu; Yuheng Wang (Journal of Environmental Sciences, 2023)

Origins of black carbon from anthropogenic emissions and open biomass burning transported to Xishuangbanna, Southwest China - Xuyan Liu; Siwen Wang; Qianqian Zhang; Chunlai Jiang; Linlin Liang; Shihao Tang; Xingying Zhang; Xiuzhen Han; Lin Zhu (Journal of Environmental Sciences, 2023)

High Fischer ratio peptide of hemp seed: Preparation and anti-fatigue evaluation in vivo and in vitro - Zhu Ying; Huang Yuyang; Li Meiying; Sun Bingyu; Liu Linlin; Lv Mingshou; Qu Min; Guan Huanan; Zhu Xiuqing (Food Research International, 2023)

Colorimetric active carboxymethyl chitosan/oxidized sodium alginate-Oxalis triangularis ssp. papilionacea anthocyanins film@gelatin/zein-linalool membrane for milk freshness monitoring and preservation - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Lanhua Liu; Shaotong Jiang; Hualin Wang (Food Chemistry, 2023)

Development of Zein/tannic acid nanoparticles as antioxidants for oxidation inhibition of blackberry seed oil emulsions - Shuangjian Li; Siyuan Li; Minhui Gong; Hongzhi Zhang; Linlin Fan; Xiaoli Liu; Jianzhong Zhou (Food Chemistry, 2023)

Arsenic Exposure, Periconceptional Folic Acid Supplementation, and the Risk for Neural Tube Defects: A Case–Control Study - Xin Pi; Chengrong Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Jufen Liu; Yali Zhang; Aiguo Ren (Exposure and Health, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Comprehensively investigating performance and potential mechanism of anammox-based nitrogen removal process with different microbial morphologies under mainstream conditions - Shuang Liu; Xinxin Xu; Hongli Li; Ming Zeng; Linlin Hao; Ruihua Zhao; Jingguo Cao; Nan Wu; Zongpeng Zhang (Journal of Environmental Chemical Engineering, 2023)

Insight into the design and construction of Cr substituted Co-based columnar activated coke catalysts for effective and reliable removal of methylbenzene and Hg0 concurrently - Lei Gao; Lei Yi; Dong Xie; Hanqing Wang; Caiting Li; Linlin Li; Yijin Liu; Jinke Xie; Yihui Zhou; Yingyun Liu (Fuel, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

Regulation of MIL-88B(Fe) to design FeS2 core-shelled hollow sphere as high-rate anode for a full sodium-ion battery - Linlin Ma; Baoxiu Hou; Hui Zhang; Shitao Yuan; Bin Zhao; Yuan Liu; Xinran Qi; Haiyan Liu; Shuaihua Zhang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

Short telomeres impede germ cell specification by upregulating MAPK and TGFβ signaling - Chenglei Tian; Dai Heng; Nannan Zhao; Linlin Liu; Xiaoyan Sheng; Jiyu Chen; Lin Liu (Science China Life Sciences, 2023)

Cenozoic plants from Tibet: An extraordinary decade of discovery, understanding and implications - Zhekun Zhou; Jia Liu; Linlin Chen; Robert A. Spicer; Shufeng Li; Jian Huang; Shitao Zhang; Yongjiang Huang; Linbo Jia; Jinjin Hu; Tao Su (Science China Earth Sciences, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Heterosis in growth and low temperature tolerance in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Shuai Chen; Yongsheng Tian; Zhentong Li; Yang Liu; Ziqi Li; Pengfei Duan; Linlin Li; Xinyi Wang; Linna Wang; Xinlei He; Xia Zhao; Wensheng Li; et al. (Aquaculture, 2023)

Methylmercury promotes oxidative stress and autophagy in rat cerebral cortex: Involvement of PI3K/AKT/mTOR or AMPK/TSC2/mTOR pathways and attenuation by N-acetyl-L-cysteine - Yanfeng Wei; Linlin Ni; Jingjing Pan; Xiaoyang Li; Yu Deng; Bin Xu; Tianyao Yang; Jingyi Sun; Wei Liu (Neurotoxicology and Teratology, 2023)

Data quality evaluation and calibration of on-road remote sensing systems based on exhaust plumes - Shijie Liu; Xinlu Zhang; Linlin Ma; Liqiang He; Shaojun Zhang; Miaomiao Cheng (Journal of Environmental Sciences, 2023)

Different nitrogen fertilizer application in the field affects the morphology and structure of protein and starch in rice during cooking - Shijie Shi; Gaoyu Zhang; Linlin Chen; Wenhui Zhang; Xiaodong Wang; Keqiang Pan; Lina Li; Jing Wang; Juan Liu; Cougui Cao; Yang Jiang (Food Research International, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Divergent responses of Qinghai spruce (Picea crassifolia) to recent warming along elevational gradients in the central Qilian Mountains, Northwest China - Weiguo Zhang; Xiaohua Gou; Fen Zhang; Wenhuo Liu; Yun Zhang; Linlin Gao (Journal of Geographical Sciences, 2023)

Whether increased water‐use efficiency of Picea crassifolia promotes radial growth of trees in the eastern Qilian Mountains - Kai Wang; Xiaohua Gou; Linlin Gao; Wenhuo Liu; Haowen Fan; Weiguo Zhang; Haijiang Yang (International Journal of Climatology, 2022)
Global change, characterized by elevated atmospheric CO 2 concentrations and warming, is profoundly affecting terrestrial forests. However, whether the increasing atmospheric CO 2 concentration has a fertilizer effect on tree growth and whether intrinsic water use efficiency (iWUE) promotes tree growth in semi‐arid regions is not entirely clear. In this study, we evaluated the relationships between tree‐ring widths, δ 13 C values and iWUE of Qinghai Spruce ( Picea crassifolia Kom.) in the eastern Qilian Mountains, northwestern China. We found that the iWUE is significantly consistent with the δ 13 C of rings in the high‐frequency signal, and the relationship between iWUE and tree‐ring width is unstable. The first‐order difference correlation analysis with meteorological data showed that both the iWUE and tree‐ring width were drought‐limited. The radial growth was mainly regulated by water availability in current April and July, while annual variation of iWUE was primarily controlled by that in current July. In the early stage of trees growth, there was a positive relationship between iWUE and radial growth due to the CO 2 fertilization. During the 1970s–2000s, the effect of water availability in July on radial growth increases because of the decreased precipitation in July. This has decreased stomatal conductance, intercellular CO 2 concentration, carbon uptake and growth, contributing to the negatively significant correlation between tree‐ring widths and iWUE ( p

High-quality chromosome-level genome assembly of Pacific cod, Gadus macrocephalus - Yiqing Ma; Yuan Li; Chen Jiang; Li Zheng; Shenghao Liu; Linlin Zhao (Frontiers in Marine Science, 2022)

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Influence of the indirect assimilation of radar reflectivity data using the ensemble Kalman filter on the simulation of a warm-sector squall line - Xuexing Qiu; Chun Liu; Zhixin He; Linlin Zheng (Meteorology and Atmospheric Physics, 2022)
Radar data assimilation is an important method to improve the performance of numerical models in severe convective weather. In this study, the statistical relationships between the radar reflectivity intensity and the latent heat release intensity and humidity are calculated based on Weather Research and Forecasting (WRF) model forecast results. Then, they are used to convert the radar reflectivity observation data into the virtual observation of the temperature and humidity. Finally, these data are continuously assimilated to the initial field of the WRF model using the ensemble Kalman filter to simulate a warm-sector squall line process. The results show that the temperature and humidity in the strong radar echo area are adjusted after the radar reflectivity data are assimilated, and new convective echoes can be excited quickly in a short time. The indirect assimilation of the radar reflectivity data can effectively improve the forecast skills of both the warm-sector squall line and the influence time of the squall line. After the assimilation, the forecast results of the influence time of the squall line on the downstream regions are basically consistent with the observations. At the same time, the forecast skills of the squall line intensity and the surface gust intensity are improved. The forecast results of the experiments with different influence radii are all better than those without radar reflectivity assimilation. When the influence radius is smaller, the improvement lasts longer. When the influence radius is larger, the improvement is more significant in the now-casting period with a shorter duration. The simulation skill of this squall line is high with an influence radius of 25 km. In addition, the assimilation of the virtual observation of both the temperature and humidity can improve the forecast skill of the squall line, especially the virtual observation with the assimilation of the humidity.

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

Improving precipitation ensemble forecasts of typhoon heavy rainfall over East China with a modified probability-matching technique - Chun Liu; Hanqing Deng; Xuexing Qiu; Linlin Zheng; Yajun Lu; Ying Zhang (Bulletin of Atmospheric Science and Technology, 2022)

Core rhizosphere microbiome of Panax notoginseng and its associations with belowground biomass and saponin contents - Guangfei Wei; Guozhuang Zhang; Mengzhi Li; Congsheng Liu; Fugang Wei; Yong Wang; Zhixin Huang; Zhongjian Chen; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Microbiology, 2022)
The core rhizosphere microbiome is critical for plant fitness. However, its contribution to the belowground biomass and saponin contents of Panax notoginseng remains unclear. High‐throughput sequencing of amplicon and metagenome was performed to obtain the microbiome profiles and functional traits in P. notoginseng rhizosphere across a large spatial scale. We obtained 639 bacterial and 310 fungal core OTUs, which were mainly affected by soil pH and organic matter (OM). The core taxa were grouped into four ecological clusters (i.e. high pH, low pH, high OM and low OM) for sharing similar habitat preferences. Furthermore, structural equation modelling (SEM) and correlation analyses revealed that the diversity and composition of core microbiomes, as well as the metagenome‐derived microbial functions, were related to belowground biomass and saponin contents. Key microbial genera related to the two plant indicators were also identified. In short, this study explored the main driving environmental factors of core microbiomes in the P. notoginseng rhizosphere and revealed that the core microbiomes and microbial functions potentially contributed to the belowground biomass and saponin contents of the plant. This work may enhance our understanding of interactions between microbes and perennial plants and improve our ability to manage root microbiota for the sustainable production of herbal medicine.

Operation performance of an ultralow-temperature cascade refrigeration freezer with environmentally friendly refrigerants R290-R170 - Haihui Tan; Lingfei Xu; Linlin Yang; Minkai Bai; Zhan Liu (Environmental Science and Pollution Research, 2022)

A decision-support system for recycling of residents’ waste plastics in China based on material flow analysis and life cycle assessment - Manzhi Liu; Jixin Wen; Linlin Zhang; Jixin Wu; Xiaotao Yang; Ying Qin; Yingjie Liu (Environmental Science and Pollution Research, 2022)

Alteration of alpha and beta diversity in nekton community by extreme marine heatwave events: An example from the East China Sea - Zunlei Liu; Linlin Yang; Liping Yan; Hui Zhang; Yi Zhang; Min Xu; Yan Jin; Jiahua Cheng (Frontiers in Marine Science, 2022)
In the year of 2016 to 2017, record-breaking marine heatwave (MHW) events occurred along the Chinese coast, exerting severe impacts on coastal fishes and fisheries. However, the response of the nekton community to MHW events still remains poorly understanding. Thus, to investigate the influences of the MHW events on species composition dynamics, this study conducted a survey on nekton communities in the northern East China Sea in the summers during 2014 to 2017. The recently-developed “heatwaveR” package was adopted to describe the variation characteristics of heatwaves within the study area, based on high-resolution remote-sensing sea surface temperature products. We also compared variations in the community structures of different biological groups before (2014–2015) and during the occurrence of the MHW events (2016–2017). During the MHW events, temperature increased by approximately 2.3°C in both 2016 and 2017. Compared with those before the MHW events, the biomass and dominance of several important crustaceans decreased, and the biomass of warm water affinity species increased significantly, while their richness and diversity decreased; the biomass of warm temperature affinity species declined significantly, while their diversity increased slightly. These results show the difference in the response rates of species with different thermal preferences and different species compositions to the extreme climate change. Beta diversity analysis revealed that the inter-group variation before and during the MHW event exceeded the intra-group variation, proving that MHWs changed the community structure to a certain extent. PERMANOVA test showed that the species compositions of planktivorous fish (FG1) and small-omnivorous fish (FG2) in the feeding-functional groups were significantly different before and during the MHW event, which may be attributed to the impact of MHWs on oligotrophic fishes through thermal preference and the trophic cascade effect. There was no significant change in the species compositions of other functional groups, indicating that medium-trophic and eutrophic fishes possessed certain adaptability to MHWs. Regarding fisheries management under extreme warming events, it would be advisable to diagnose temperature anomalies in the early stage, monitor changes in species abundance in the early life cycle, and then rapidly develop suitable fishing strategies.

LaeA regulates morphological development and ochratoxin A biosynthesis in Aspergillus niger - Mengwei Zhang; Yan Yang; Linlin Li; Shuwen Liu; Xianli Xue; Qiang Gao; Depei Wang; Ying Zhang; Jian Zhang (Mycotoxin Research, 2022)

Identification and functional analysis of two GJA8 variants in Chinese families with eye anomalies - Linlin Zhou; Xuejiao Sun; Xinyao Wang; Kangyu Liu; Zilin Zhong; Jianjun Chen (Molecular Genetics and Genomics, 2022)

Incorporating egg-transporting pathways into conservation plans of spawning areas: An example of small yellow croaker (Larimichthys polyactis) in the East China Sea zone - Zunlei Liu; Yan Jin; Linlin Yang; Liping Yan; Yi Zhang; Min Xu; Jianhua Tang; Yongdong Zhou; Fen Hu; Jiahua Cheng (Frontiers in Marine Science, 2022)
Backward-in-time Lagrangian model can identify potential spawning areas by reconstructing egg drift trajectories, contributing to accurately designing potential priority conservation plans for spawning areas. In this study, we apply this approach to investigate the small yellow croaker ( Larimichthys polyactis ) with commercial value in China. A two-step spatial random forest (RF) model is used to predict the occurrence probability and abundance of their eggs and describe the optimal ecological range of environmental factors. A priority protection index (BPPI) of the spawning areas is established by combining the sites with the optimal occurrence and abundance and integrating backward tracking pathways. The result indicates that the model with 1-2 day time lags of environmental variables shows the optimum explanatory power. Temperature and salinity are the most important factors affecting oogenesis and show a regime shift in the response curve. They reflect the physiological regulation of parental sexual maturation by the environment. In addition, egg abundance correlates more strongly with chlorophyll-a (Chl a) concentration and depth, suggesting that parents prefer environments with shallow water and high prey density for spawning activities. The egg retrieval shows that the potential spawning sources are distributed near the southeastern part of the oogenesis site, with a maximum egg dispersal distance of no more than 30 km. This finding confirms that the coastal regions of Jiangsu Province are an important spawning ground for the small yellow croaker, making a significant contribution to the productivity and resilience of the fish.

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

Estimating the impacts of climate change on the habitat suitability of common minke whales integrating local adaptation - Bin Sun; Linlin Zhao; Fei Shao; Zhichuang Lu; Jiashen Tian; Changdong Liu (Frontiers in Marine Science, 2022)
Climate change is exerting unprecedented effects on the habitats of marine mammals. Common minke whales ( Balaenoptera acutorostrata ) have suffered immense harm from commercial whaling, and the recovery of this species is likely threatened by climate change. To better manage and conserve this species, it is important to predict its current habitat distribution and the potential change under future climate change scenarios. Such predictions are typically generated by species distribution models (SDMs), which construct a correlation between species occurrence data and its habitat environmental variables. SDMs are commonly constructed at the species level, assuming a homogenous response of the species to climatic variables across their entire geographic range. Spatially segregated populations from the same species inhabit distinct environments and gradually adapt to the local conditions, resulting in niche differentiation among populations. Species-level SDMs that ignore the effects of local adaptation mask differences in population responses to climate change and might present an unrealistic picture of potential species distributions. Based on morphological and genetic evidence, the common minke whale was divided into three populations: the North Atlantic population (NAP), Southern Hemisphere population (SHP) and North Pacific population (NPP); these populations inhabit isolated geographic areas with distinct environmental conditions. We quantified the realized niches of these populations and found evidence of significant ecological niche differentiation. We then constructed SDMs at the species and population levels and compared the predictions from these two types of models under different climate change scenarios. Both types of models projected similar change trends in species range, with a contraction of future suitable habitats for the NAP and SHP and an expansion for the NPP. However, the magnitudes of this change differed; the population-level model projected more optimistic results for the SHP and NAP, indicating less habitat loss. This study highlighted the importance of considering local adaptation when estimating the impact of climate change on species habitat suitability. These spatiotemporal predictions provide essential knowledge for designing climate-adaptive conservation and management strategies, such as the delimitation of mobile marine protected areas (MPAs).

Construction of a mutant Bacillus subtilis strain for high purity poly-γ-glutamic acid production - Linlin He; Lu Liu; Rui Ban (Biotechnology Letters, 2022)

Chromosomal Assembly of the Hexagrammos agrammus Genome via Third-Generation DNA Sequencing and Hi-C Technology - Linlin Zhao; Shenghao Liu; Shouqiang Wang; Tianyan Yang; Qi Liu; Tianxiang Gao (Frontiers in Marine Science, 2022)

Traditional fermented soybean products: processing, flavor formation, nutritional and biological activities - Libo Liu; Xiaoqian Chen; Linlin Hao; Guofang Zhang; Zhao Jin; Chun Li; Yuzhuo Yang; Jiajia Rao; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2022)

Drinking water elements constituent profiles and health risk assessment in Wuxi, China - Keqin Wu; Yuanhua Meng; Yan Gong; Linlin Wu; Wenwei Liu; Xinliang Ding (Environmental Monitoring and Assessment, 2022)

QpefBD: A Benchmark Dataset Applied to Machine Learning for Minute-Scale Quantitative Precipitation Estimation and Forecasting - Anyuan Xiong; Na Liu; Yujia Liu; Shulin Zhi; Linlin Wu; Yongjian Xin; Yan Shi; Yunjian Zhan (Journal of Meteorological Research, 2022)

Characterizing the Semi-Volatile Organic Compounds in Runoff from Roads and Other Impervious Surfaces in a Suburban Area of Beijing - Liang Zhang; Haiyan Li; Youshu Wang; Zhichao Yang; Ziyang Zhang; Fei Liu; Linlin Tong; Ying Wang; Yongwei Gong; Hua Yang (Archives of Environmental Contamination and Toxicology, 2022)

Identifying Priority Conservation Areas of Largehead Hairtail (Trichiurus japonicus) Nursery Grounds in the East China Sea - Zunlei Liu; Yan Jin; Liping Yan; Yi Zhang; Hui Zhang; Chuyi Shen; Linlin Yang; Jiahua Cheng (Frontiers in Marine Science, 2022)
Identifying the spatio-temporal distribution hotspots of fishes and allocating priority conservation areas could facilitate the spatial planning and efficient management. As a flagship commercial fishery species, Largehead hairtail ( Trichiurus japonicus ) has been over-exploited since the early 2000s. Therefore, the spatio-temporal management of largehead hairtail nursery grounds could effective help its recovery. This study aims to predict juvenile largehead hairtail distribution patterns and identify priority conservation areas for nursery grounds. A two-stage hierarchical Bayesian spatio-temporal model was applied on independent scientific survey data (Catch per unit effort, CPUE) and geographic/physical variables (Depth, Distance to the coast, Sea bottom temperature, Dissolved oxygen concentration and Net primary production) to analyze the probability of occurrence and abundance distribution of juvenile largehead hairtail. We assessed the importance of each variable for explaining the occurrence and abundance. Using persistence index, we measured the robustness of hotspots and identified persistent hotspots for priority conservation areas. Selected models showed good predictive capacity on occurrence probability (AUC = 0.81) and abundance distribution ( r = 0.89) of juvenile largehead hairtail. Dissolved oxygen, net primary production, and sea bottom temperature significantly affected the probability of occurrence, while distance to the coast also affected the abundance distribution. Three stable nursery grounds were identified in Zhejiang inshore waters, the largest one was located on the east margin of the East China Sea hairtail national aquatic germplasm resources conservation zones (TCZ), suggesting that the core area of nursery grounds occurs outside the protected areas. Therefore, recognition of these sites and their associated geographic/oceanic attributes provides clear targets for optimizing largehead hairtail conservation efforts in the East China Sea. We suggested that the eastern and southern areas of TCZ should be included in conservation planning for an effective management within a network of marine protected areas.

Effects of Smooth Cordgrass Spartina alterniflora Invasion on Macrobenthic Fauna in the Yellow River Delta - Shaoyu Jiang; Chuanxin Zhang; Linlin Chen; Chunyun Liu; Lang Yan; Baoquan Li (Wetlands, 2022)

Save reservoirs of humid subtropical cities from eutrophication threat - Meijie Liu; Xiaoyu Lei; Yanyan Zhou; Jingsi Gao; Yun Zhou; Linlin Wang; Jia Zhu; Xian-zhong Mao (Environmental Science and Pollution Research, 2022)

Deep convolutional neural network with random field model for lake ice mapping from Sentinel-1 imagery - Zhiguo Ma; Zihao Liu; Jiabin Pu; Linlin Xu; Kui Li; Linglong Wangqu; Rui Wu; Yiyi Ma; Ye Chen; Claude Duguay (International Journal of Remote Sensing, 2021)

Isocitrate dehydrogenase of Bacillus cereus is involved in biofilm formation - Linlin Zhao; Qing Liu; Qiubin Huang; Fengying Liu; Huiping Liu; Gang Wang (World Journal of Microbiology and Biotechnology, 2021)

Correction to: Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC‑7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC-7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

A July-August relative humidity record in North China since 1765 AD reconstructed from tree-ring cellulose δ18O - Linlin Cui; Yu Liu; Qiang Li; Huiming Song; Congxi Fang (International Journal of Biometeorology, 2021)

Relationship between heavy metal consolidation and H2S removal by biochar from microwave pyrolysis of municipal sludge: effect and mechanism - Qingyuan Lin; Jun Zhang; Linlin Yin; Hao Liu; Wei Zuo; Yu Tian (Environmental Science and Pollution Research, 2021)

The behavioral and antioxidant response of the bivalve Gomphina veneriformis to sediment burial effect - Xiaojing Li; Linlin Chen; Zhengquan Zhou; Baoquan Li; Xin Liu (Acta Oceanologica Sinica, 2021)

Domain decomposition based on the spectral element method for frequency-domain computational elastodynamics - Linlin Shi; Mingwei Zhuang; Yuanguo Zhou; Na Liu; Qinghuo Liu (Science China Earth Sciences, 2021)

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Utilization of serum procalcitonin as a biomarker in the diagnosis and treatment of children with bacterial hospital-acquired pneumonia - Wenlong Wang; Yitang Zhu; Linlin Yin; Yaoyao Deng; Guoxian Chu; Supin Liu (Molecular and Cellular Biochemistry, 2021)

Spatio-temporal variation of subtidal macrobenthic fauna and the ecological assessment of Longkou Artificial Island construction in Bohai Sea, China - Xiaojing Li; Linlin Chen; Zhengquan Zhou; Baoquan Li; Xin Liu; Lufei Yang; Bo Liu; Bo Song (Journal of Oceanology and Limnology, 2020)

Enhanced mass transfer and service time of mesh Ti/Sb-SnO2 electrode for electro-catalytic oxidation of phenol - Linlin Huang; Da Li; Junfeng Liu; Lisha Yang; Changchao Dai; Nanqi Ren; Yujie Feng (Environmental Science and Pollution Research, 2020)

The immune response to a recombinant Lactococcus lactis oral vaccine against foot-and-mouth disease virus in mice - Xinsheng Liu; Linlin Qi; Jianliang Lv; Zhongwang Zhang; Peng Zhou; Zhongyuan Ma; Yonglu Wang; Yongguang Zhang; Li Pan (Biotechnology Letters, 2020)

A benchmark city for seismic resilience assessment - Qingxue Shang; Xiaodong Guo; Quanwang Li; Zhen Xu; Linlin Xie; Chaofeng Liu; Jichao Li; Tao Wang (Earthquake Engineering and Engineering Vibration, 2020)

High throughput detection of antibiotic residues in milk by time-resolved fluorescence immunochromatography based on QR code - Asha Ashuo; Wenjia Zou; Jingjie Fu; Tengkun Yang; Linlin Yu; Wei Liu; Liu Yang; Ghulam Mujtaba Mari; Haiyang Jiang (Food Additives & Contaminants: Part A, 2020)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Adaptive feeding in the American oyster Crassostrea virginica : Complex impacts of pulsatile flow during pseudofecal ejection events - Linlin Wang; Junting Song; Hongsheng Bi; Matthew Gray; Chunlei Fan; Ming Liu; Xian‐Zhong Mao (Limnology and Oceanography, 2020)
Adaptive feeding is a strategy used by many organisms to maintain growth and reproduction success while encountering varying feeding conditions. Oysters are sessile benthic and non‐siphon filter feeders. Oysters are well adapted to modify the ambient microenvironment through their pumping behavior and particle selection activity. Rejection of unsuitable food particulates bound in pseudofeces via ejection events are an integral part of oyster feeding during which oysters produced strong flow opposite to their inhalant feeding flow. The strong opposite pulsatile flow during the ejection event inevitably disrupts the oyster's normal feeding cycle, but how oysters restart their feeding and allocate their energy consumption during an ejection event has not been investigated. The present study used particle image velocimetry (PIV) to examine the impact of ejection events on the feeding of the American oyster, Crassostrea virginica . The strong pulsatile flow resulting from pseudofecal ejection altered the external flow fields by moving water away from the shell. The initial feeding zone after pseudofecal ejection was relatively narrow, possessed a low pulsatile flow, and did not exploit the full flow field. The feeding zone gradually expanded as the pulsatile flow weakened. The strong shear rate at the stable feeding zone then sustained the feeding flow that facilitated oyster feeding. Furthermore, the volumetric fluxes often increased after the ejection event, suggesting increase in feeding efficiency after ejection events. These PIV studies provide new insight on the interactions between feeding oysters and the surrounding physical environment at small yet ecologically relevant scales.

DNA Methylation Analysis of the NR3C1 Gene in Patients with Schizophrenia - Linlin Liu; Jian Wu; Lili Qing; Jiajue Li; Hao Yang; Aicen Ji; Ming Yan; Liping Hu; Shengjie Nie (Journal of Molecular Neuroscience, 2020)

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Dynamic features of near-inertial oscillations in the Northwestern Pacific derived from mooring observations from 2015 to 2018 - Shijian Hu; Lingling Liu; Cong Guan; Linlin Zhang; Jianing Wang; Qingye Wang; Jie Ma; Fujun Wang; Fan Jia; Junqiao Feng; Xi Lu; Fan Wang; et al. (Journal of Oceanology and Limnology, 2020)

Quality by Design–Based Assessment for Analytical Similarity of Adalimumab Biosimilar HLX03 to Humira® - Erhui Zhang; Liqi Xie; Peilan Qin; Lihong Lu; Yanpeng Xu; Wenyuan Gao; Linlin Wang; Michael Hongwei Xie; Weidong Jiang; Scott Liu (The AAPS Journal, 2020)
Quality by design (QbD) is an efficient but challenging approach for the development of biosimilar due to the complex relationship among process, quality, and efficacy. Here, the analytical similarity of adalimumab biosimilar HLX03 to Humira® was successfully established following a QbD quality study. Quality target product profile (QTPP) of HLX03 was first generated according to the public available information and initial characterization of 3 batches of Humira®. The critical quality attributes (CQAs) were then identified through risk assessment according to impact of each quality attribute on efficacy and safety. The anticipated range for each CQA was derived from similarity acceptance range and/or the corresponding regulatory guidelines. Finally, a panel of advanced and orthogonal physicochemical and functional tests and comparison of 6 batches of HLX03 and 10 batches of the reference standard demonstrated high similarity of HLX03 to Humira®, except for slightly lower percentage of high mannosylated glycans (%HM) in HLX03 which had no effect on FcγRIII binding and antibody-dependent cell-mediated cytotoxicity (ADCC) activity in human peripheral blood mononuclear cell (PBMC). All above demonstrated the feasibility and efficiency of QbD-based similarity assessment of a biosimilar monoclonal antibody (mAb).

NLRP3 Deficiency Attenuates Secondary Degeneration of Visual Cortical Neurons Following Optic Nerve Injury - Zhou Zhang; Wenyi Liu; Yubin Huang; Linlin Luo; Xiaofeng Cai; Yunjia Liu; Liqianyu Ai; Jun Yan; Sen Lin; Jian Ye (Neuroscience Bulletin, 2020)

Cutibacterium acnes Type II strains are associated with acne in Chinese patients - Shuyang Zhao; Jiayu Ci; Jinhui Xue; Yaofeng Wang; Xuelong Li; Linlin Hao; Liu Tian; Haiyan Guo; Chengqi Xin; Yujie Zhao (Antonie van Leeuwenhoek, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Four superoxide dismutases of Bacillus cereus 0–9 are non-redundant and perform different functions in diverse living conditions - Juanmei Zhang; Haodong Wang; Qiubin Huang; Ying Zhang; Linlin Zhao; Fengying Liu; Gang Wang (World Journal of Microbiology and Biotechnology, 2020)

Evaluation of Genomic Selection for Seven Economic Traits in Yellow Drum (Nibea albiflora) - Guijia Liu; Linsong Dong; Linlin Gu; Zhaofang Han; Wenjing Zhang; Ming Fang; Zhiyong Wang (Marine Biotechnology, 2019)
Yellow drum ( Nibea albiflora ) is an important maricultural fish in China, and genetic improvement is necessary for this species. This research evaluated the application of genomic selection methods to predict the genetic values of seven economic traits for yellow drum. Using genome-wide single-nucleotide polymorphisms (SNPs), we estimated the genetic parameters for seven traits, including body length (BL), swimming bladder index (SBI), swimming bladder weight (SBW), body thickness (BT), body height (BH), body length/body height ratio (LHR), and gonad weight index (GWI). The heritability estimates ranged from 0.309 to 0.843. We evaluated the prediction performance of various statistical methods, and no one method provided the highest predictive ability for all traits. We then evaluated and compared the use of genome-wide association study (GWAS)–informative SNPs and random SNPs for prediction and found that GWAS-informative SNPs obviously increased. It only needed 5 and 100 informative SNPs for LHR and BT to achieve almost the same predictive abilities as using genome-wide SNPs, and for BL, SBI, SBW, BH, and GWI, about 1000 to 3000 informative SNPs were needed to achieve whole-genome level predictive abilities. It can be concluded from the test results that breeders can use fewer SNPs to save the breeding costs of genomic selection for some traits.

Effects of Vitamin E and Selenium on Growth Performance, Antioxidant Capacity, and Metabolic Parameters in Growing Furring Blue Foxes (Alopex lagopus) - Keyuan Liu; Hanlu Liu; Ting Zhang; Linlin Mu; Xueqing Liu; Guangyu Li (Biological Trace Element Research, 2019)

Influence of High Relative Humidity on Secondary Organic Carbon: Observations at a Background Site in East China - Linlin Liang; Guenter Engling; Yuan Cheng; Xiaoye Zhang; Junying Sun; Wanyun Xu; Chang Liu; Gen Zhang; Hui Xu; Xuyan Liu; Qianli Ma (Journal of Meteorological Research, 2019)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

Ozonation catalyzed by iron- and/or manganese-supported granular activated carbons for the treatment of phenol - Wei Xiong; Nan Chen; Chuanping Feng; Yang Liu; Ningping Ma; Jian Deng; Linlin Xing; Yu Gao (Environmental Science and Pollution Research, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Xylitol Production by Candida tropicalis 31949 from Sugarcane Bagasse Hydrolysate - Linlin Xu; Lei Liu; Sijia Li; Wenjing Zheng; Yuanyuan Cui; Rong Liu; Weidong Sun (Sugar Tech, 2019)

Identification of protein arginine methyltransferase 7 (PRMT7) inhibitor by virtual screening and biological evaluation in vitro - Linlin Liu; Xiaoning Kai; Qingqing Chen; Ling Zhang; Ruosi Yao; Jian Gao (Medicinal Chemistry Research, 2019)

Heat Transfer in Sandstones at Low Temperature - Zhiqiang Liu; Linlin Wang; Bo Zhao; Jingyi Leng; Guangqing Zhang; Diansen Yang (Rock Mechanics and Rock Engineering, 2019)

Ascorbic acid induces cardiac differentiation of white adipose tissue-derived stem cells - Wenhui Liu; Huan Liu; Yinghui Wang; Linlin Zhang; Chunhui Wang; Haifang Li (Molecular and Cellular Biochemistry, 2019)

A novel long non-coding RNA, lncKBTBD10, involved in bovine skeletal muscle myogenesis - Mingming Chen; Xin Li; Xiaojuan Zhang; Yan Li; Junxing Zhang; Minhui Liu; Linlin Zhang; Xiangbin Ding; Xinfeng Liu; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Constitutive activation of β-catenin in ameloblasts leads to incisor enamel hypomineralization - Linlin Fan; Shijian Deng; Xin Sui; Mengmeng Liu; Shuhua Cheng; Yunfei Wang; Yuguang Gao; Chun-Hung Chu; Qi Zhang (Journal of Molecular Histology, 2018)

Effect of polysaccharides extracted from Sipunculus nudus (SNP) on the lifespan and immune damage repair of Drosophila melanogaster exposed to Cd (VI) - Jie Su; Linlin Jiang; Jingna Wu; Zhiyu Liu; Yuping Wu (Natural Product Research, 2018)

Fermentation Kinetics of Enzymatic Hydrolysis Bagasse Solutions for Producing l-Lactic Acid - Yuanyuan Cui; Rong Liu; Linlin Xu; Wenjing Zheng; Weidong Sun (Sugar Tech, 2018)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

Prevalence and trend of isolated and complicated congenital hydrocephalus and preventive effect of folic acid in northern China, 2005–2015 - Jufen Liu; Lei Jin; Zhiwen Li; Yali Zhang; Le Zhang; Linlin Wang; Aiguo Ren (Metabolic Brain Disease, 2018)

The impact of urbanization on wind speed and surface aerodynamic characteristics in Beijing during 1991–2011 - Junkai Liu; Zhiqiu Gao; Linlin Wang; Yubin Li; Chloe Y. Gao (Meteorology and Atmospheric Physics, 2018)

Osteoprotegerin deficiency causes morphological and quantitative damage in epithelial rests of Malassez - Yunfei Wang; Mengmeng Liu; Shijian Deng; Xin Sui; Linlin Fan; Qi Zhang (Journal of Molecular Histology, 2018)

Linkage disequilibrium and functional analysis of PRE1 insertion together with SNPs in the promoter region of IGFBP7 gene in different pig breeds - Qingyan Wu; Hao Yu; Wenzhen Wei; Yunyun Cheng; Shan Huang; Hongyu Shi; Songcai Liu; Jichao Xia; Hongyao Jia; Linlin Hao (Journal of Applied Genetics, 2018)

Macrobenthic assemblage characteristics under stressed waters and ecological health assessment using AMBI and M-AMBI: a case study at the Xin’an River Estuary, Yantai, China - Zhengquan Zhou; Xiaojing Li; Linlin Chen; Baoquan Li; Tiantian Liu; Binghua Ai; Lufei Yang; Bo Liu; Qiao Chen (Acta Oceanologica Sinica, 2018)

Reduced deep regional cerebral venous oxygen saturation in hemodialysis patients using quantitative susceptibility mapping - Chao Chai; Saifeng Liu; Linlin Fan; Lei Liu; Jinping Li; Chao Zuo; Tianyi Qian; E. Mark Haacke; Wen Shen; Shuang Xia (Metabolic Brain Disease, 2018)

Definition and classification system of glacial lake for inventory and hazards study - Xiaojun Yao; Shiyin Liu; Lei Han; Meiping Sun; Linlin Zhao (Journal of Geographical Sciences, 2018)

Three new oleanane-type triterpenoid saponins from the seeds of Celosia cristata L. - Xin Liu; Jifa Zhang; Kai Guo; Airong Jia; Miansong Zhang; Yaping Shi; Changheng Liu; Linlin Xiao; Zhenliang Sun (Natural Product Research, 2018)

MicroRNA-192 regulates hypertrophic scar fibrosis by targeting SIP1 - Yan Li; Julei Zhang; Wei Zhang; Yang Liu; Yuehua Li; Kejia Wang; Yijie Zhang; Chen Yang; Xiaoqiang Li; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Identification and Functional Analysis of Two Cotton Orthologs of MAX2 Which Control Shoot Lateral Branching - Linlin Zhao; Jingjing Fang; Jin Xing; Weina Liu; Peng Peng; Haixin Long; Jinfeng Zhao; Wenhui Zhang; Xueyong Li (Plant Molecular Biology Reporter, 2017)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

A lncRNA promotes myoblast proliferation by up-regulating GH1 - Yingwei Yue; Congfei Jin; Mingming Chen; Linlin Zhang; Xinfeng Liu; Wenzhi Ma; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Assessing the wavelength-dependent ability of solar-induced chlorophyll fluorescence to estimate the GPP of winter wheat at the canopy level - Liangyun Liu; Xinjie Liu; Jiaochan Hu; Linlin Guan (International Journal of Remote Sensing, 2017)

Disposition of Flavonoids for Personal Intake - Shuqiang Liu; Haihui Zheng; Rongjin Sun; Huangyu Jiang; Jiamei Chen; Jia Yu; Qisong Zhang; Qingwei Chen; Lijun Zhu; Ming Hu; Linlin Lu; Zhongqiu Liu (Current Pharmacology Reports, 2017)

Exosomes derived from human amniotic epithelial cells accelerate wound healing and inhibit scar formation - Bin Zhao; Yijie Zhang; Shichao Han; Wei Zhang; Qin Zhou; Hao Guan; Jiaqi Liu; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Effects of maize stover and its derived biochar on greenhouse gases emissions and C-budget of brown earth in Northeast China - Xu Yang; Yu Lan; Jun Meng; Wenfu Chen; Yuwei Huang; Xiaoyi Cheng; Tianyi He; Ting Cao; Zunqi Liu; Linlin Jiang; Jiping Gao (Environmental Science and Pollution Research, 2017)

Gelatin microspheres containing calcitonin gene-related peptide or substance P repair bone defects in osteoporotic rabbits - Jianghao Chen; Wei Liu; Jinxiu Zhao; Cong Sun; Jie Chen; Kaijin Hu; Linlin Zhang; Yuxiang Ding (Biotechnology Letters, 2017)

Characterization of harpinXoo induced hypersensitive responses in non host plant, tobacco - Linlin Xie; Yue Liu; Hui Wang; Wenbo Liu; Rong Di; Weiguo Miao; Fucong Zheng (Journal of Plant Biochemistry and Biotechnology, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Short communication: antiviral activity of porcine IFN-λ3 against porcine epidemic diarrhea virus in vitro - Haiyan Shen; Chunhong Zhang; Pengju Guo; Zhicheng Liu; Minhua Sun; Junying Sun; Linlin Li; Jiawen Dong; Jianfeng Zhang (Virus Genes, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Probing the structure and dynamics of caveolin-1 in a caveolae-mimicking asymmetric lipid bilayer model - Hanqi Liu; Linlin Yang; Qiansen Zhang; Lingxue Mao; Hualiang Jiang; Huaiyu Yang (European Biophysics Journal, 2016)

Zircon ages and Hf isotopic compositions of Permian and Triassic A-type granites from central Inner Mongolia and their significance for late Palaeozoic and early Mesozoic evolution of the Central Asian Orogenic Belt - Yuruo Shi; J. Lawford Anderson; Linlin Li; Jing Ding; Cui Liu; Wei Zhang; Chonghui Shen (International Geology Review, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Allogeneic adipose-derived stem cells promote survival of fat grafts in immunocompetent diabetic rats - Jun Zhang; Xiaozhi Bai; Bin Zhao; Yunchuan Wang; Linlin Su; Peng Chang; Xujie Wang; Shichao Han; Jianxin Gao; Xiaolong Hu; Dahai Hu; Xiaoyan Liu (Cell and Tissue Research, 2016)

Role of Exogenous Nitric Oxide in Alleviating Iron Deficiency Stress of Peanut Seedlings (Arachis hypogaea L.) - Jing Kong; Yuanjie Dong; Yiling Song; Xiaoying Bai; Xianyi Tian; Linlin Xu; Shuang Liu; Zhenli He (Journal of Plant Growth Regulation, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Forward modeling analyses of Qilian Juniper (Sabina przewalskii) growth in response to climate factors in different regions of the Qilian Mountains, northwestern China - Junzhou Zhang; Xiaohua Gou; Yongxiang Zhang; Ming Lu; Xiangyu Xu; Fen Zhang; Wenhuo Liu; Linlin Gao (Trees, 2016)

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma - Chunhua Wan; Chen Gong; Li Ji; Xiaorong Liu; Yayun Wang; Liang Wang; Mengting Shao; Linlin Yang; Shaoqing Fan; Yin Xiao; Xiaotong Wang; Manhua Li; et al. (Molecular and Cellular Biochemistry, 2015)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Structural control on pore-fracture characteristics of coals from Xinjing coal mine, northeastern Qinshui basin, China - Jiegang Liu; Bo Jiang; Ming Li; Zhenghui Qu; Linlin Wang; Lei Li (Arabian Journal of Geosciences, 2015)

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids - Peimin Dai; Lijun Zhu; Feifei Luo; Linlin Lu; Qiang Li; Liping Wang; Ying Wang; Xinchun Wang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2015)

Highly sensitive fluorescence biosensors for sparfloxacin detection at nanogram level based on electron transfer mechanism of cadmium telluride quantum dots - Wanjun Liang; Shaopu Liu; Jing Song; Chenxia Hao; Linlin Wang; Dan Li; Youqiu He (Biotechnology Letters, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

A comparison of de-noising methods for differential phase shift and associated rainfall estimation - Zhiqun Hu; Liping Liu; Linlin Wu; Qing Wei (Journal of Meteorological Research, 2015)

Contrasting characteristics of the surface energy balance between the urban and rural areas of Beijing - Linlin Wang; Zhiqiu Gao; Shiguang Miao; Xiaofeng Guo; Ting Sun; Maofeng Liu; Dan Li (Advances in Atmospheric Sciences, 2015)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Full and ideal mixing behavior between Zr–Wd (K2ZrSi3O9) and Ti–Wd (K2TiSi3O9): evidences from mineral chemistry, X-ray diffraction pattern and Raman spectrum - Linlin Chang; Xi Liu; Chunming Wu; Xiaoyang Liu; Guowu Li (Physics and Chemistry of Minerals, 2015)

Effects of Exogenous Salicylic Acid on Alleviating Chlorosis Induced by Iron Deficiency in Peanut Seedlings (Arachis hypogaea L.) - Jing Kong; Yuanjie Dong; Linlin Xu; Shuang Liu; Xiaoying Bai (Journal of Plant Growth Regulation, 2014)

Organochlorine pesticide contamination in marine organisms of Yantai coast, northern Yellow Sea of China - Jing Chen; Linlin Chen; Dongyan Liu; Gaosheng Zhang (Environmental Monitoring and Assessment, 2014)

Effects of Exogenous Salicylic Acid and Nitric Oxide on Physiological Characteristics of Perennial Ryegrass Under Cadmium Stress - Quanhui Wang; Xue Liang; Yuanjie Dong; Linlin Xu; Xiuwei Zhang; Jing Kong; Shuang Liu (Journal of Plant Growth Regulation, 2013)

Lanthanum chloride impairs spatial learning and memory and downregulates NF-κB signalling pathway in rats - Linlin Zheng; Jinghua Yang; Qiufang Liu; Fei Yu; Shengwen Wu; Cuihong Jin; Xiaobo Lu; Lifeng Zhang; Yanqiu Du; Qi Xi; Yuan Cai (Archives of Toxicology, 2013)

Rhizobacteria (Pseudomonas sp. SB) assist phytoremediation of oily-sludge-contaminated soil by tall fescue (Testuca arundinacea L.) - Wuxing Liu; Jianying Sun; Linlin Ding; Yongming Luo; Mengfang Chen; Caixian Tang (Plant and Soil, 2013)

Vibrational mode analysis and heat capacity calculation of K2SiSi3O9-wadeite - Linlin Chang; Xi Liu; Hong Liu; Hiroshi Kojitani; Sicheng Wang (Physics and Chemistry of Minerals, 2013)

Polybrominated Diphenyl Ethers Contamination in Marine Organisms of Yantai Coast, Northern Yellow Sea of China - Jing Chen; Linlin Chen; Dongyan Liu; Gaosheng Zhang (Bulletin of Environmental Contamination and Toxicology, 2013)

Calcium accumulation characterization in the aerobic granules cultivated in a continuous-flow airlift bioreactor - Dandan Zhou; Mengyuan Liu; Linlin Gao; Chunyan Shao; Jie Yu (Biotechnology Letters, 2013)

Climate–growth analysis of Qilian juniper across an altitudinal gradient in the central Qilian Mountains, northwest China - Linlin Gao; Xiaohua Gou; Yang Deng; Wenhuo Liu; Meixue Yang; Zhiqian Zhao (Trees, 2013)

Expansivity and compressibility of wadeite-type K2Si4O9 determined by in situ high T/P experiments, and their implication - Linlin Chang; Zhiqiang Chen; Xi Liu; Hejing Wang (Physics and Chemistry of Minerals, 2013)

Overexpression of GbWRKY1 positively regulates the Pi starvation response by alteration of auxin sensitivity in Arabidopsis - Li Xu; Li Jin; Lu Long; Linlin Liu; Xin He; Wei Gao; Longfu Zhu; Xianlong Zhang (Plant Cell Reports, 2012)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Heavy metal contamination in the marine organisms in Yantai coast, northern Yellow Sea of China - Gaosheng Zhang; Dongyan Liu; Huifeng Wu; Linlin Chen; Qingxi Han (Ecotoxicology, 2012)

Propagation characteristic of atmospheric responses to abnormal warm SST in the Kuroshio Extension in winter - Wang Xiaodan; Zhong Zhong; Liu Jianwen; Qi Linlin (Theoretical and Applied Climatology, 2012)

Identification and Analysis of Muscle-Related Protein Isoforms Expressed in the White Muscle of the Mandarin Fish (Siniperca chuatsi) - Guoqiang Zhang; Wuying Chu; Songnian Hu; Tao Meng; Linlin Pan; Renxue Zhou; Zhen Liu; Jianshe Zhang (Marine Biotechnology, 2011)

Variable length LMS adaptive filter for carrier phase multipath mitigation - Huicui Liu; Xiaojing Li; Linlin Ge; Chris Rizos; Feixue Wang (GPS Solutions, 2011)

Left ventricular hypertrophy induced by abdominal aortic banding and its prevention by angiotensin receptor blocker telmisartan—a proteomic analysis - Li Liu; Wen Wang; Xianmin Meng; Jiuming Gao; Haiying Wu; Peihe Wang; Weichun Wu; Linlin Wang; Liyuan Ma; Weiguo Zhang (Journal of Physiology and Biochemistry, 2010)

A Critical Role of Src-Suppressed C Kinase Substrate in Rat Astrocytes After Chronic Constriction Injury - Yinyin Xia; Haiou Liu; Aiguo Shen; Yonghua Liu; Linlin Sun; Tao Tao; Qing Ke; Chun Cheng (NeuroMolecular Medicine, 2010)

Regulation of Cell Division and Growth in Roots of Lactuca sativa L. Seedlings by the Ent-Kaurene Diterpenoid Rabdosin B - Lan Ding; Hongwei Jing; Bo Qin; Linlin Qi; Jing Li; Tao Wang; Guoan Liu (Journal of Chemical Ecology, 2010)

Distribution of borehole temperature at four high-altitude alpine glaciers in Central Asia - Yaping Liu; Shugui Hou; Yetang Wang; Linlin Song (Journal of Mountain Science, 2009)

The expression of analgesic-antitumor peptide (AGAP) from Chinese Buthus martensii Karsch in transgenic tobacco and tomato - Linlin Lai; Tingting Huang; Yi Wang; Yanfeng Liu; Jinghai Zhang; Yongbo Song (Molecular Biology Reports, 2009)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Increased expression of CDK11p58 and cyclin D3 following spinal cord injury in rats - Yuhong Ji; Feng Xiao; Linlin Sun; Jing Qin; Shuxian Shi; Junling Yang; Yonghua Liu; Dan Zhou; Jian Zhao; Aiguo Shen (Molecular and Cellular Biochemistry, 2008)

Lipopolysaccharide induces expression of SSeCKS in rat lung microvascular endothelial cell - Chun Cheng; Haiou Liu; Haiyan Ge; Ji Qian; Jing Qin; Linlin Sun; Menling Chen; Meijuan Yan; Aiguo Shen (Molecular and Cellular Biochemistry, 2007)

Lipopolysaccharide-Induced Upregulation of Tumor Necrosis Factor-α (TNF-α) and TNF Receptors in Rat Sciatic Nerve - Youhua Wang; Dan Zhou; Qin Shen; Chun Cheng; Hai-ou Liu; Yongwei Qin; Linlin Sun; Feng Xiao; Jian Zhao; Aiguo Shen (Journal of Molecular Neuroscience, 2007)

Expression of phytoene synthase gene (Psy) is enhanced during fruit ripening of Cara Cara navel orange (Citrus sinensis Osbeck) - Nengguo Tao; Zhiyong Hu; Qin Liu; Juan Xu; Yunjiang Cheng; Linlin Guo; Wenwu Guo; Xiuxin Deng (Plant Cell Reports, 2007)